Systems and methods for composite solid-state battery cells with ion-conducting polymer electrolytes

By adopting solid electrolytes in lithium-ion batteries and optimizing the combined process of electrodes and electrolyte layers, the problems of flammability and high porosity of liquid electrolytes are solved, and higher energy density and power characteristics are achieved.

CN114342146BActive Publication Date: 2025-04-29A123 SYSTEMS LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080061717.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-01
Filing Date
2020-07-01
Publication Date
2025-04-29
Estimated Expiration
2040-07-01

AI Technical Summary

Technical Problem

The liquid electrolytes in existing lithium-ion batteries are flammable, causing safety problems, and their high porosity leads to an increase in resistance, affecting the energy density and power characteristics of the battery.

Method used

Solid electrolytes are used to replace liquid electrolytes, and by optimizing the particle distribution and combination process of the electrode and electrolyte layer, the porosity is reduced and the electrochemical capacity is improved.

Benefits of technology

It effectively reduces the flammability risk of the battery, improves the energy density and power characteristics, and enhances the mechanical stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114342146B_ABST
    Figure CN114342146B_ABST
Patent Text Reader

Abstract

Systems and methods for coating slurries of electrode structures are provided. In one example, a method may include dispersing a solid ion conductive polymer material in a first portion of a solvent by mixing at one or both of high shear and low shear to form a suspension, then dispersing one or more additives in the suspension by mixing at one or both of high shear and low shear, and then mixing a second portion of the solvent with the suspension at one or both of high shear and low shear to form a slurry. Thus, a slurry including a solid ion conductive polymer material can be applied as a coating in a solid-state battery cell, which can reduce resistance to lithium ion transport and improve mechanical stability relative to conventional solid-state battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related technologies

[0002] This application claims priority to U.S. Provisional Application No. 62 / 869,407, entitled “SYSTEMS AND METHODS FOR A COMPOSITE SOLID-STATE BATTERY CELL WITH AN IONICALLY CONDUCTIVE POLYMER ELECTROLYTE” and filed on July 1, 2019. The entire contents of the above application are incorporated herein by reference for all purposes. Technical Field

[0003] The present description generally relates to systems and methods for solid-state battery cells including ion-conducting polymer materials.

[0004] Background and Summary of the Invention

[0005] The energy density of a secondary battery is an important figure of merit because it describes how much work can be performed per unit mass or volume when calculated by weight or volume, respectively. In the case of automotive applications, these metrics are important because they specify how far the car can travel before it needs to be recharged, relative to how much of the car's total mass or volume is dedicated to modules responsible for the car's energy reserve.

[0006] The energy density of a composite energy storage device is affected by the theoretical weight or volume capacity of the electrode active material and the amount (mass or volume) of the electrode active material contained therein. In addition, the packaging efficiency of the materials comprising the energy storage device affects the energy density, whereby inefficiency may be manifested in the form of porosity or free volume, which for a given capacity is manifested in the form of increased volume, or in the case of a fixed volume, resulting in a decrease in capacity. Since the voids within the electrode or dielectric layer destroy the path along which the charged species move, the porosity or free volume produced by inefficient packaging also has the effect of increasing resistance. As the internal resistance increases, the power characteristics of the battery decrease, resulting in a decrease in performance when high charge or discharge rates are required. In the case of conventional lithium-ion batteries, a given degree of porosity can be accepted and even functional because this space is permeated by a liquid electrolyte to facilitate the transfer of lithium ions from the active material of one electrode to the other. Although this medium for ion transport provides a high level of mobility for lithium ions, it has the disadvantage of being highly flammable, resulting in safety issues in automotive or other transportation applications.

[0007] The desire to eliminate the risks associated with the flammability of the liquid electrolyte components of conventional lithium-ion batteries has led to interest in replacing the liquid electrolyte with a solid electrolyte, with the result that any non-functional free volume needs to be eliminated from the overall battery structure in order to optimize the above-mentioned performance characteristics. For example, solid electrolytes exist in a variety of forms, including inorganic oxides and sulfides and organic materials, which include a continuum of media in form from gel polymers to solid polymers.

[0008] The inventors have recognized the above problems and have identified solutions that at least partially address these problems. To achieve a dense structure, including a group of particulate materials, including but not limited to subgroups of organic and inorganic components of electrode active materials, solid polymer electrolytes, conductive additives, adhesives, and other functional or passive properties, the inventors have recognized that the particle size distribution of the individual components and their relative percentages of the total solid volume can be carefully selected. These criteria help optimize the inter-particle packing and their distribution relative to each other to maintain the functionality of the constituent materials. In addition to the a priori design of the particle groups, either alone or in combination with each other, it is most important to consider the combination process of these materials because they affect the size and proximal distribution of the materials in composite form. The process aspects of combining the component materials include reagents introduced to promote mixing and formation, the order of combining the component groups, and methods for manipulating the components (including mixtures thereof).

[0009] The design criteria and manufacturing methods of each layer of the energy storage device may vary depending on the required functions of each layer. For example, for some applications, an electrode including a mixture of powders of electrode active materials, solid electrolytes and conductive additives and other components can be configured based on a group of electrode active particles in a group of smaller solid electrolyte and conductive additive particles. In this configuration, the particle size and distribution parameters can be selected to provide a layer with low porosity while also establishing a percolative network of solid electrolytes and conductive additives to support ionic and electronic conduction, respectively. In order to meet the functional requirements of the electrode layer, the design must maximize the energy content by establishing a major group of electrode active materials, wherein the solid electrolyte and conductive additives are dispersed in the continuous phase so that connectivity between the gaps of the electrode active particles can be achieved. In this case, the volume occupied by the solid electrolyte and conductive additive particles can be sufficient to wedge apart the electrode active material particles to provide a percolation path without introducing unnecessary void space or occupying an excessive percentage of the solid volume, thereby limiting the electrochemical capacity achieved by the layer. To meet such construction and performance criteria, the groups of electrode active materials can be designed to establish the main phase based on the larger particle size, while the groups of smaller particles occupy a portion of the free volume between the large particles of electrode active material. The size distribution of other components and the relative percentages of the groups can be treated as the situation in the connection network between the larger groups of electrode active material particles.

[0010] In contrast, the unique functionality of the separator dictates a different set of design criteria so that it can provide the lowest possible resistance to lithium transport between electrodes while also acting as a mechanical barrier between the electrodes to prevent short circuits. The resistance to lithium transport between electrodes can be minimized by preparing the electrolyte layer with a material having a high lithium conductivity value, in which case the electrolyte layer can also act as a separator. The resistance to lithium migration can also be reduced by increasing the contact area between the electrode layer and the dielectric and by reducing the thickness of the dielectric layer. In addition, configuring the particles forming the dielectric layer to reduce the tortuosity of the path of lithium ions from one electrode to the other can reduce the resistance of the dielectric / separator layer. If the solid electrolyte is not required to be packed into the gaps between the electrode active materials, as is the case with the electrode layer, the particle size distribution used to optimize the electrolyte layer design can be different from the particle size distribution selected for the electrode layer.

[0011] Methods for differentially tuning the size distribution and relative fractions of the component materials in the electrode and electrolyte layers may provide opportunities for further configuration optimization by inserting an interfacial layer between the electrolyte and electrode layers to facilitate matching of these layers in the most efficient manner. As an example, the particle size distribution of the solid electrolyte in the interfacial layer between the electrode and electrolyte layers may be adjusted to accommodate the surface morphology of the electrode layer to provide an optimal balance between design criteria, thereby facilitating minimization of interfacial void space while also reducing the tortuosity of the percolation network that provides connectivity between the boundaries of the electrode and dielectric layers.

[0012] Optimal design of the battery's layers can result in significantly different properties between the layers, requiring exceptional flexibility in the manufacturing process to achieve the maximum potential functionality of each of these layers in combination. In addition to identifying manufacturing methods that meet this required flexibility, significant adjustments to the parameters that define how each of these technologies are deployed present a significant and non-intuitive challenge for practitioners responsible for manufacturing solid-state batteries. This article describes methods for manufacturing solid-state batteries, their component layers, and the mixtures and materials from which they are derived.

[0013] As an example and as detailed herein, a coated hybrid electrode is provided that provides at least some of the above solutions. In one example, a method of forming a slurry may include dividing a solvent into a plurality of portions according to a sequence of steps, mixing a solid ion conductive polymer material in a first portion of the solvent to form a suspension, for example, formed of polyphenylene sulfide or a liquid crystal polymer, the solid ion conductive polymer material having a relative humidity greater than 1 x 10 -5S / cm ion conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is about half of the total solvent content, the first additive is mixed in the suspension, and after the first additive is mixed in the suspension, the second portion of the solvent is mixed with the suspension to form a slurry with a solid content between 25 and 80 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2800 cps at 85 Hz, wherein the mixing includes mixing under high shear and mixing under low shear, the low shear being between 10 and 55 rpm. In this way, the slurry can be applied as a coating on an electrode structure, which can reduce porosity by optimized particle distribution compared to conventional solid-state batteries, and improve the percolation network by selectively introducing components in stages during the formation process. In addition, the use of solid ion conductive polymer materials can further reduce resistance to lithium ion transport and improve mechanical stability in battery cells including coated electrode structures.

[0014] It should be understood that the above summary is provided to introduce a selection of concepts further described in the detailed description in a simplified form. It is not meant to identify key or essential features of the claimed subject matter, the scope of which is solely defined by the claims that follow the detailed description. Furthermore, the claimed subject matter is not limited to embodiments that address any disadvantages noted above or in any part of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1A A schematic block diagram showing a first example configuration of a coated hybrid electrode.

[0016] Figure 1B A schematic block diagram showing a second example configuration of a coated hybrid electrode.

[0017] Figure 2 A first example method for forming a slurry for applying a coating on an electrode structure is shown.

[0018] Figure 3 A second example method for forming a slurry for applying a coating to an electrode structure is shown.

[0019] Figure 4 A third example method of forming a slurry for applying a coating to an electrode structure is shown.

[0020] Figure 5 An example method of forming a coating on an electrode structure via a slurry-based coating process is shown.

[0021] Figure 6 Shown is a graph depicting a bimodal particle size distribution in a slurry of cathode material coating.

[0022] Figure 7 Shown is a graph depicting the particle size distribution in a slurry of cathode material coating.

[0023] Figure 8 Shown is a graph depicting viscosity versus shear rate in a slurry of cathode material coating.

[0024] Fig. 9 A process flow diagram showing a slurry for forming a cathode material coating.

[0025] Fig.10 Scanning electron microscope (SEM) image showing particle size distribution in a slurry of cathode material coating.

[0026] Fig.11 Shown is a graph depicting the particle size distribution in a slurry of anode material coating.

[0027] Fig.12 Shown is a graph depicting viscosity versus shear rate in a slurry of anode material coating.

[0028] Fig.13 A first process flow diagram of a slurry for forming a coating of anode material is shown.

[0029] Fig.14 A second process flow diagram is shown for forming a slurry for a coating of anode material.

[0030] Fig.15 Shown is a graph depicting the particle size distribution in a slurry for a spacer coating.

[0031] Fig.16 Shown is a graph depicting viscosity versus shear rate in a slurry for a spacer coating.

[0032] Fig.17 A first process flow diagram of a slurry for forming a spacer coating is shown.

[0033] Fig.18 A second process flow diagram for forming a spacer coating slurry is shown.

[0034] Fig.19 SEM image showing particle size distribution in spacer coating slurry. DETAILED DESCRIPTION

[0035] The following description relates to systems and methods for solid-state battery cells including ion-conducting polymer materials as electrolytes. Specifically, the ion-conducting polymer material can be a solid ion-conducting powder, such as a solid ion-conducting polymer material, U.S. Patent Application Publication No. 2017 / 0018781, International Patent Publication No. 2016 / 196873, and U.S. Patent Application Publication No. 2017 / 0005356, the contents of which are incorporated herein by reference, such as a solid ion-conducting powder produced by Ionic Materials Inc. of Woburn, Massachusetts. The solid ion-conducting polymer material can be synthesized from a polymer, a dopant, and an ionic compound. The base polymer can be semi-crystalline or fully crystalline. Typical materials that can be used for the base polymer include liquid crystal polymers and polyphenylene sulfide (also referred to as PPS) or semi-crystalline polymers having a crystallinity index greater than 30% or greater than 50%. Candidate liquid crystal polymer materials for the base polymer may include copolymers of p-hydroxybenzoic acid. Other candidate base polymers include poly (p-phenyloxyphenylene ether), polyetheretherketone, polyphthalamide, polypyrrole, polyaniline, polysulfone, copolymers including monomers of the listed materials, and mixtures thereof. The solid ion conductive material can be a thermoplastic material. The solid ion conductive material conducts electricity in a glassy state. The dopant is an electron acceptor and can be DDQ, TCNE, chloroaniline, oxygen, ozone, and sulfur trioxide (SO3). The ion source or "ionic compound" can include salts commonly used in lithium-ion batteries or other battery systems, such as LiTFSI (lithium bistrifluoromethanesulfonamide), LiFSI (lithium bis (fluorosulfonyl) imide), lithium bis (oxalate) borate (LiB (C2O4) 2, "LiBOB") and other lithium ion compounds and combinations thereof. Specifically, the solid ion conductive polymer material can have a relative humidity greater than 1x 10 -5 S / cm ion conductivity, and can have a glassy state at room temperature. Therefore, the ion conductive polymer material can have high room temperature ion conductivity, and can be incorporated into various coatings of solid-state battery cells in a tunable and electrode-specific manner to achieve electrochemical stability. In addition, the ion conductive polymer material can retain the form of a solid powder, which can be insoluble in commonly used solvents. Therefore, the ion conductive polymer material can adjust / reduce the interface impedance by changing the particle size distribution, particle morphology, relative volume percentage, etc. Within the scope of the present invention, other solid polymer materials with similar functions and properties can be substituted.

[0036] As described and used in more detail herein, a battery may include an electrochemical storage device capable of converting chemical energy into electrical energy. A secondary battery may include a battery that, when a discharged state is reached, can be returned to a charged state by applying an external current or voltage according to a given set of prescribed criteria. A battery may include a plurality of battery cells configured to be electrically coupled to each other. Each cell may include at least two electrode layers and a spacer layer. Each electrode may include an electrode active material. The positive electrode active layer may be referred to as a cathode. The negative electrode active layer may be referred to as an anode.

[0037] Additionally, as described in more detail herein with respect to processes, the spacer layer may be referred to as a spacer. The spacer layer may be responsible for preventing contact between the cathode layer and the anode layer, as well as promoting transport of ionic species between the electrodes while inhibiting transport of electronic species between the electrodes.

[0038] The spacer layer may comprise an ion-conducting polymer, in particular, a solid ion-conducting polymer material, for example, one having an ion conductivity greater than 1 x 10 -5 S / cm and a crystallinity index of at least about 30%, wherein the material is in a glass state at room temperature and is formed of a polyphenylene sulfide polymer or a liquid crystal polymer. As used herein, when referring to a numerical value, "about" or "approximately" may include a deviation of 5% or less.

[0039] It will be appreciated that external electrical contact to the electrodes may be established through current collectors onto which the electrode layers are coated during the manufacturing process.

[0040] Additional layers may be introduced into the unit structure to improve the interface between the electrode layer and the separator or collector layer. As described above, each layer of the unit structure can be described by its components. For the purpose of consistency, the following conventions are used in the present invention to describe the composition layer as a whole:

[0041] - Composition (total) = component A + component B + component C + component D, wherein,

[0042] oComponent A: electrode active material;

[0043] o Component B: solid polymer electrolyte material or ion conductive solid polymer;

[0044] o Component C: free volume; and

[0045] o Component D: All other materials used in the paste formulation and layer manufacturing, including:

[0046] ■D1: Adhesive material,

[0047] ■D2: electronic conductor or conductive additive,

[0048] ■D3: Surfactant,

[0049] ■D4: solvent,

[0050] ■D5: Ceramic ion conductor (used to reduce impedance),

[0051] ■D6: Inorganic ceramics (for enhanced mechanical integrity),

[0052] ■D7: lithium salt, and

[0053] ■D8: Ion conductive additive.

[0054] Figure 1A and Figure 1B Various configurations of coated hybrid electrodes or battery cell subcomponents are depicted. Figures 6 to 8 , Figures 10 to 12 , Fig.15 , Fig.16 and Fig.19 Depicted are graphs showing various properties of the composite slurries described herein. Figures 2 to 4 Example methods are described for forming a composite slurry for applying a coating to an electrode structure (eg, a cathode material coating, an anode material coating, a cathode current collector, an anode current collector, or a combination thereof), wherein the electrode structure can subsequently be incorporated into a battery cell. Fig. 9 , Fig.13 , Fig.14 , Fig.15 and Fig.18 An example process flow diagram for forming a composite slurry is depicted. Figure 5 An example method of forming a coating on an electrode structure via a slurry-based coating process is depicted.

[0055] Reference now Figure 1A , depicting a first configuration of coated hybrid electrodes or battery cell subcomponents 100. In order, the first configuration of coated hybrid electrodes 100 may include an anode current collector 101, an anode material coating 102, an anode separator interface coating 106, a separator coating 103, a cathode separator interface coating 107, a cathode material coating 104, and a cathode current collector 105. Thus, the separator coating 103 may serve as a battery separator.

[0056] One or more of the anode material coating 102 and the anode separator interface coating 106 may include an anode active material containing lithium. One or more of the cathode material coating 104 and the cathode separator interface coating 107 may include a cathode active material containing lithium. As described above, one or more of the anode material coating 102, the anode separator interface coating 106, the separator coating 103, the cathode separator interface coating 107, and the cathode material coating 104 may include an ion conductive polymer material or another solid polymer material.

[0057] In some examples, an adhesion interface may be defined between the spacer coating 103 and the electrode structure. The adhesion interface may be a three-dimensional interface between the spacer coating 103 and the electrode structure, such that the spacer coating 103 may conform to and penetrate the surface of the electrode structure. As a first example, the electrode structure may be an anode material coating 102 deposited on an anode current collector 101, and optionally, an anode spacer interface coating 106 may be deposited thereon. As a second example, the electrode structure may be a cathode material coating 104 deposited on a cathode current collector 105, and optionally, a cathode spacer interface coating 107 may be deposited thereon. In some examples, the 180° peel strength of the adhesion interface may be greater than 200 gf / in. Therefore, the slurry-based coating method described herein may produce greater adhesion than applying a separate polymer electrolyte membrane (which may have a 180° peel strength of about 2.1 gf / in in some examples).

[0058] Reference now Figure 1B , depicting a second configuration 150 of coated hybrid electrodes or battery cell subcomponents. In order, the second configuration 150 of coated hybrid electrodes may include an anode current collector 101, an anode material coating 102, an anode separator interface coating 106, a first separator coating 103a, a conventional battery separator 108, a second separator coating 103b, a cathode separator interface coating 107, a cathode material coating 104, and a cathode current collector 105. In some examples, the conventional battery separator 108 may be separated into a single separator coating 103.

[0059] Figure 2 A first method 200 for forming a slurry including a solid ion conductive polymer material is provided. In some examples, the slurry can be applied as a coating on an electrode structure by a slurry-based coating process. In some examples, the coating can be one of a cathode material coating, a cathode spacer interface coating, an anode spacer interface coating, and a spacer coating, such as cathode material coating 104, anode material coating 102, cathode spacer interface coating 107, anode spacer interface coating 106, and spacer coating 103, as described above with respect to Figure 1A and Figure 1B described.

[0060] In some examples, the first method 200 can use multiple mixers, wherein the multiple mixers can be configured to perform 202 to 206, as described in detail below. Each of the multiple mixers can operate at one or both of high shear and low shear. In addition, in some examples, 202 to 206 can be performed in sequence, i.e., from 202 to 204 to 206.

[0061] At 202, a solid ion-conducting polymer material (e.g., component B) can be dispersed in at least a first portion of a solvent (e.g., component D4) to form a suspension. In some examples, at least a first portion of the solvent can include one or more other components. Thus, the first portion of the solvent can include a solution.

[0062] At 204, one or more additives may be dispersed in the suspension. In some examples, the one or more additives may include an electrode active material (e.g., component A), a binder (e.g., component D1), a surfactant (e.g., component D3), and an inorganic ceramic (e.g., component D6).

[0063] At 206, a second portion of the solvent may be mixed with the suspension to form a slurry. A second portion of the solvent may be provided to achieve a target solid content. Thus, in some examples, the slurry may have a solid content between 40 and 80 wt.%, a d10 particle size distribution less than 1 μm, a d50 particle size distribution less than 30 μm, a d90 particle size distribution less than 60 μm, and a d99 particle size distribution less than 140 μm. The Hegman gauge is less than 90 μm, and the viscosity is between 500 and 280 cps at 85 Hz. Then, the first method 200 may end.

[0064] Reference now Figure 3 , describes a second method 300 for forming a slurry including a solid ion conductive polymer material. In some examples, the slurry can be applied as a coating on the electrode structure by a slurry-based coating process. In some examples, the coating can be one of a cathode material coating, a cathode spacer interface coating, and an anode spacer interface coating, such as cathode material coating 104, anode material coating 102, cathode spacer interface coating 107, and anode spacer interface coating 106, as described above with respect to Figure 1A and Figure 1B described.

[0065] In some examples, the second method 300 can use multiple mixers, wherein the multiple mixers can be configured to perform 302 to 310, as described in detail below. Each of the multiple mixers can operate at one or both of high shear and low shear. In addition, in some examples, 302 to 310 can be performed in sequence, i.e., from 302 to 304 to 306 to 308 to 310.

[0066] At 302 , a first portion of a binder (eg, component D1 ) may be dissolved in a first portion of a solvent (eg, component D4 ) to form a solution.

[0067] At 304 , a conductive additive (eg, component D2 ) may be dispersed in the first portion of the solution to form a suspension.

[0068] At 306 , a solid ionically conductive polymer material (eg, component B) and a second portion of the solution may be dispersed in the suspension.

[0069] At 308, one or more other additives and the remainder of the solution can be dispersed in the suspension. In some examples, the one or more other additives can include an electrode active material (eg, component A) and a second portion of the binder (eg, component D1).

[0070] At 310, a second portion of the solvent may be mixed with the suspension to form a slurry. The second portion of the solvent may be provided to achieve a target solid content. Thus, in some examples, the slurry may have a solid content between 40 and 80 wt.%, a d10 particle size distribution of less than 10 μm, a d50 particle size distribution of less than 30 μm, a d90 particle size distribution of less than 60 μm, a d99 particle size distribution of less than 140 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2800 cps at 85 Hz. The second method 300 may then end.

[0071] Reference now Figure 4 , describing a third method 400 for forming a slurry including a solid ion-conducting polymer material. In some examples, the slurry can be applied as a coating on an electrode structure by a slurry-based coating process. In some examples, the coating can be a spacer coating, such as described above with reference to Figure 1A and Figure 1B The spacer coating 103 .

[0072] In some examples, the third method 400 can use multiple mixers, wherein each of the multiple mixers can be configured to perform 402 to 412, as described in detail below. Each of the multiple mixers can operate at one or both of high shear and low shear. In addition, in some examples, 402 to 412 can be performed in sequence, i.e., from 402 to 404 to 406 to 408 to 410 to 412.

[0073] At 402, a solid ion-conducting polymer material (e.g., component B) can be dispersed in at least a first portion of a solvent (e.g., component D4) to form a suspension. In some examples, at least a first portion of the solvent can include one or more other components. Thus, the first portion of the solvent can include a solution.

[0074] At 404, the binder (e.g., component D1) and the surfactant (e.g., component D3) can be dissolvents in the second portion of the solvent. At 406, the inorganic ceramic (e.g., component D6) can be dissolved in the second portion of the solvent to form a solution. At 408, a portion of the solution can be dispersed in the suspension. At 410, the remainder of the solution can be dispersed in the suspension.

[0075] In some examples, at 412, a third portion of the solvent may be mixed with the suspension to form a slurry. The third portion of the solvent may be provided to achieve a target solids content. Thus, in some examples, the slurry may have a solids content between 40 and 55 wt.%, a d10 particle size distribution of less than 1 μm, a d50 particle size distribution of less than 15 μm, a d90 particle size distribution of less than 60 μm, a d99 particle size distribution of less than 100 μm, a Hegman gauge of less than 90 μm, and a viscosity of between 500 and 2200 cps at 85 Hz. The third method 400 may then end.

[0076] Figure 5 Another method 500 for forming a coating on an electrode structure by a slurry-based coating process is provided, whereby the electrode structure may be included in a battery cell. In some examples, the coating may be one of a cathode material coating, a cathode spacer interface coating, an anode spacer interface coating, and a spacer coating, such as cathode material coating 104, anode material coating 102, cathode spacer interface coating 107, anode spacer interface coating 106, and spacer coating 103, as described above with respect to Figure 1A and Figure 1B In other examples, the coating may form one of a first tab protection strip and a second tab protection strip for the anode current collector and the cathode current collector (eg, the anode current collector 101 and the cathode current collector 105), respectively, as described above with reference to Figure 1A and Figure 1B described.

[0077] At 502, a slurry including a solid ion conductive polymer material (e.g., component B) can be obtained. In some examples, the slurry can be the composite slurry described above, and can also include one or more of component A, component C, and component D. In some examples, the slurry can be in liquid form.

[0078] At 504, the slurry may be applied to the electrode structure. In some examples, the electrode structure may include an anode current collector (e.g., 101), a cathode current collector (e.g., 105), a previously deposited anode material coating (e.g., 102), a previously deposited cathode material coating (e.g., 104), or a previously deposited separator coating (e.g., separator coating 103, anode separator interface coating 106, cathode separator interface coating 107, etc.) A variety of slurry-based coating processes may be used without departing from the scope of the present invention, including but not limited to slot die coating, roll-to-roll coating (e.g., gravure coating, screen printing, flexographic printing), doctor blade casting, tape casting, spray (aerosol) coating, reverse comma coating, etc.

[0079] At 506, the coated electrode structure can be dried, and at 508, the coated electrode structure can be calendered. Within the scope of the present invention, each of drying and calendering can be optimized to obtain a desired coating process. Method 500 can then end.

[0080] The methods described herein can be used to form unit coatings or layers. Each layer will be described in more detail below.

[0081] cathode

[0082] In one example, the cathode layer of the cell may include a variety of materials that may be characterized as powders in an isolated population, provided that a large number of particles having similar composition and properties are included. These powders may be combined with other materials to form a slurry to facilitate deposition of a continuous layer having functionality derived from its composite onto a substrate, which in the case of the present invention may be a current collector or a previously manufactured electrode, a separator, or a component comprising a combination thereof. In the following, a description of the component materials, methods by which the materials may be combined to form a slurry, properties of the slurry, and methods of casting the slurry is provided.

[0083] In one example, the composite including the cathode and its derived slurry can be formed from a combination of multiple materials with active and passive functions. Some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry coating.

[0084] The cathode composite, in slurry or other form, may be defined as follows:

[0085] - Composition (total) = Component A + Component B + Component C + Component D

[0086] -wherein component A corresponds to the cathode active material

[0087] -wherein component B corresponds to an ion-conducting solid polymer

[0088] -where component C corresponds to the free volume

[0089] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0090] Thus, the cathode slurry may include the following components:

[0091] Component A

[0092] - A combination of one or more active materials, for example one or more of the following active materials: lithium iron phosphate (LFP), spinel LNMO, LiCoPO4, LiNiPO4, LVP, LVPF, LiNixMnyCozO2 or LiNixCoAlZO2, with a primary particle size between 0.01 and 20 μm

[0093] Section B

[0094] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0095] Component C

[0096] Component D

[0097] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0098] -Component D2: electronic conductor, such as carbon black, super P, vapor-grown carbon fiber

[0099] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0100] - Component D4: one or more dispersing solvents, such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0101] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0102] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds resulting from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0103] In addition to the solvent, the cathode slurry may contain the previous components within the following ranges:

[0104] - solid ion-conducting polymer material, between 0 and 15 wt.%

[0105] - Active material, between 80 and 95 wt.%

[0106] - Binder, content between 0.1 and 10 wt.%

[0107] -Electronic conductor, between 1 and 10 wt.%

[0108] - Surfactant, content between 0 and 5 wt.%

[0109] The composite volume of the cathode layer can be defined as

[0110] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0111] - The volume percentage of component A may be >35%, >45%, >55%, >60%, or >65%

[0112] - The volume percentage of component B may be <30%, <25%, <20%, <15%, or <10%

[0113] -The volume percentage of component C may be <40%, <30%, <20%, or <15%

[0114] - The volume percentage of component D may be <30%, <25%, <10%, or <5%

[0115] - The sum of the volume percentages of components C and D may be less than 40%, <30%, <20%, or <15%

[0116] The size of the particles, including the powder form of components A and B, can also be described by:

[0117] - In the volume % comprising component A, it may be assigned an average particle size value A mean, the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0118] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0119] - In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for 100%, <95%, <85%, or <80%, and the remainder of component A, identified by A2, belongs to A 2,mean mean Groups of particles located in the spaces between larger particles

[0120] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0121] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0122] - In the volume % including component B, the size distribution is determined by the average value B 1,mean >B mean The particles of the group described in the form account for >80%, <85%, <90%, or <95%, and the remainder of component B, identified by B2, belongs to B 2,mean mean Groups of particles located in the spaces between larger particles

[0123] The relative fractions of component A and component B that make up the complex (total) can be described as follows:

[0124] - As the volume % of component A (including the percentage of total solid volume) increases, the volume % of component B (including B2) will increase relative to the volume % of component B (including B1). This approach can reduce the porosity level

[0125] ​​- As the ratio of component A1 to component A2 decreases, the ratio of the volume % of component B (including B1) to the volume % of component B (including B2) can be reduced. In some examples, this approach maintains the solid polymer electrolyte perocolation network as the surface of the active material grows while maintaining the SPE:AM density by also reducing the size ratio of B1:B2.

[0126] - The fraction of component A added to the complex (total) in the form of A1 may be 100%, <95%, <90%, <85% or <80%

[0127] - The fraction of component B added to the complex (total) in the form of B1 may be 100%, <90%, <80%, <70%, <60% or <50%

[0128] Prior to its coating, in some examples, the positive electrode slurry may be characterized as:

[0129] - Viscosity between 1000 and 2600 cps at 85 Hz, measured by parallel plate rheometer.

[0130] - Solids content between 45% and 75%

[0131] -Hegman gauge below 80μm or below 5μm

[0132] - Particle size distribution is as follows: d10 < 10 μm, d50 < 30 μm, d90 < 60 μm, d99 < 100 μm

[0133] In a low humidity environment, the rolling can be performed between room temperature (20° C.) and 140° C. The thickness of the positive electrode after rolling can be between 100 and 400 μm.

[0134] Representative particle size distribution curves are shown in Figure 2. Figure 6 The graph of 600 and Figure 7 The first peak represents the particle size of component B, while the second peak at about 10 μm is attributed to component A.

[0135] Representative viscosity curves are as follows: Figure 8 800, where viscosity is plotted against shear rate. In this example, the slurry exhibits shear thinning.

[0136] Cathode Mixed Slurry Method

[0137] An example procedure for forming a cathode slurry is provided below.

[0138] Example of a cathode slurry mixing process Procedure 1: In this example, component D1 (binder) can be added as a solution in multiple stages.

[0139] i. Mixing speed and equipment

[0140] Specifically, the dispersion of the components can be achieved by a combination of a single-shaft mixer equipped with a sawtooth high-shear disperser and a multi-shaft mixer equipped with multiple high-shear dispersers and a low-shear anchor mixer or a low-shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0141] ■ Low shear shaft between 10 and 55 rpm

[0142] ■High shear shaft between 0 and 1500 rpm

[0143] ii. Solution of component D1 in component D4

[0144] First, component D1 can be dissolved in component D4 to form 1 and 15 wt.% solutions. Component D2 can be dispersed.

[0145] iii. Dispersed component D2

[0146] A portion of the component D1 solution (10% to 60%) and component D2 can be mixed between 30 minutes and 90 minutes. After this step, the solids content is between 5 and 30 wt.%.

[0147] iv. Dispersed component B

[0148] Then, another portion (5% to 40%) of the component B and component D1 solutions can be added to the previous suspension and mixed for between 30 and 90 minutes. After this step, the solids content can be between 10 and 50 wt.%.

[0149] v. Dispersed component A

[0150] Half of component A can be added to a mixing container along with another portion of component D1 solution (10% to 70%); the solution can be mixed for another 45 to 120 minutes. After this step, the solids content can be between 40 and 80 wt.%. The other half of component A and the remainder of component D1 solution can be added to a mixing container and mixed for 120 minutes to 16 hours.

[0151] Vi, target solid percentage

[0152] In some examples, additional component D4 may be added at this time to achieve the above-mentioned final slurry properties. After the process is completed, the slurry properties may be:

[0153] ■d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0154] ■Hegman gauge <50μm

[0155] ■Solid content between 40-80wt.%

[0156] ■Viscosity between 2000 and 2600 cps at 85 Hz

[0157] The process flow chart 900 of example process 1 is as follows: Fig. 9 shown.

[0158] Example of cathode slurry mixing process Step 2: As another example, a method of adding a binder as a powder in a single stage is provided.

[0159] i. Mixing speed and equipment

[0160] In this example, dispersion of the components may be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, a low shear anchor mixer, or a low shear helical impeller.

[0161] In some embodiments, throughout the mixing process, the mixing speed may be maintained as follows:

[0162] ■ Low shear shaft between 10 and 55 rpm

[0163] ■High shear shaft between 0 and 1500 rpm

[0164] ii. Dispersed component D2

[0165] Component D4, component D1 and component D2 may be mixed for between 30 and 90 minutes. After this step, the solids content may be between 5 and 30 wt.%.

[0166] iii. Dispersed component B

[0167] Component B and more component D4 can be added to the previous suspension and mixed for between 30 and 90 minutes. After this step, the slurry solids content can be between 10 and 50 wt.%.

[0168] iv. Dispersed component A

[0169] Half of component A can be added to the mixing vessel along with more component D4. In this example, the solution can be mixed for another 45 to 120 minutes. After this step, the slurry solids content can be between 40 and 80 wt.%. The other half of component A and more component D4 can be added to the mixing vessel and mixed for 120 minutes to 16 hours.

[0170] v. Target solid percentage

[0171] In some examples, additional solvent may be added at this point to achieve the final slurry properties described above. After this step, the slurry properties may be:

[0172] ■d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0173] ■Hegman gauge <50μm

[0174] ■Solid content between 40-80wt.%

[0175] ■At 85Hz, the viscosity is between 1000 and 2000cps

[0176] Example Process 3 of Cathode Slurry Mixing Process: As another example, a process is provided that includes mixing using only a high shear disperser.

[0177] i. Mixing speed and equipment

[0178] In this example, a single-shaft mixer equipped with a sawtooth high-speed disperser can be used to achieve dispersion of the components. The high shear shaft mixing speed can be maintained between 0 and 1500 rpm throughout the mixing process.

[0179] ii. Solution of component D1 in component D4

[0180] First, component D1 can be dissolved in component D4 to form 1 and 15 wt. % solutions.

[0181] iii. Dispersed component D2

[0182] Component D1 in D4 solution can be used, wherein component D2A from the options provided above for component D2 can be dispersed first. Mixing can be for 30-90 minutes. Next, the second component (component D2B) from the options provided above for component D2 can be dispersed for another 30-90 minutes. The solid content is about 10%.

[0183] iv. Dispersed component B

[0184] Next, component B can be dispersed into the slurry for 30-90 minutes. After this step, component A can be added in its entirety, wherein the slurry can be mixed for 2-12 hours.

[0185] v. Target solid percentage

[0186] Finally, component D4 may be added to adjust the solids content of the slurry to between 50-60%.

[0187] Table 1 provides an example of a slurry mixing process.

[0188] Table 1: For LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811) (cathode active material), example of cathode slurry mixing process.

[0189]

[0190] An alternative approach has also been considered in the mixing process to distribute the solid electrolyte components. For example, in order to promote the distribution of component particles, provide optimal density and maintain the functionality of the component materials, the order in which the particle groups of different materials are added to the mixture is carefully selected. Smaller particles have a tendency to be interspersed among larger particles. In order to achieve this effectively, the uniformity of the distribution of larger particles must first be determined. In addition, in order to obtain higher gravimetric analysis capabilities, the total content of each component material can be divided into several groups to design the distribution of large particle groups relative to smaller particle groups.

[0191] Given the previous definition of the composite volume of the cathode layer, it is defined as:

[0192] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0193] -wherein component A corresponds to the cathode active material

[0194] -wherein component B corresponds to an ion-conducting solid polymer

[0195] -where component C corresponds to the free volume

[0196] -where component D corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[0197] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0198] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0199] - In the volume % comprising component B, it may be assigned an average particle size value B mean, the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0200] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0201] Taking into account the above design criteria, the order in which the components of the cathode layer are combined by a mixing process to form a mixture of components A, B, C and D is specified as follows:

[0202] Step 1, initially, component A1 can be mixed with a portion of component B2

[0203] Step 2, component A1 can be mixed with a portion of component D to provide a dispersed group of A1 particles decorated with B1 particles.

[0204] Step 3, alone or in combination with component A1, components B1 and A2 may be mixed together with a further portion of component D

[0205] Step 4, a portion of component B2 can be added to the mixture

[0206] Step 5, component B2 and the remaining portion of component D may be gradually added to the mixture until the mixture may include all of components A1, A2, B1, B2 and D.

[0207] In addition to the above, the use of a discontinuous binder medium is considered part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without inhibiting the transfer of charged species at the interface between the active material of the electrode and the ion-conductive particles dispersed throughout the battery layer or between the polymer solid particles forming the electrolyte layer.

[0208] To deploy this strategy, staged mixing is again utilized, whereby the active material for a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid electrolyte. This ion-conductive powder-coated active material can then be mixed with a binder carrier that is resistant to dissolving agents in the slurry solvent. After mixing the solid electrolyte-coated active material and the non-soluble binder carrier, an additional soluble binder component can be added to adjust the mechanical durability of the electrode without compromising the ion-conducting and electroactive material functionality.

[0209] An example of this process can be described as follows:

[0210] Step 1, initially, component A1 can be mixed with a portion of component B2

[0211] Step 2: The mixture of component A1 and component B2 can be mixed with component D 1A (insoluble binder) and a portion thereof, provided with B2 particles and D 1A (Insoluble Binder) Particle Decorated Dispersed A1 Particle Group

[0212] Step 3, a portion of B1 and component D 1B (soluble binder) is added to the mixture of component A1, component B2 and component D1 (insoluble binder)

[0213] Step 4: Components B1 and A2 may be prepared alone or in combination with components A1, B2 and D. 1A (insoluble) mixture, and further add component D 1B (Soluble adhesive) part

[0214] Step 5, a portion of component B2 can be added to the mixture

[0215] Step 6, Component B2 and Component D 1B The remainder of the mixture may be gradually added to the mixture until the mixture may include components A1, A2, B1, B2, D 1A and D 1B All

[0216] To promote the desired distribution of the above components, the following parameters can be used when using this method to guide the optimization of the component particle size distribution:

[0217] The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4.

[0218] - The most common particle size of cathode active material component A1 can be less than 20 microns, greater than 5 microns or 10 microns

[0219] - The most common particle size of cathode active material component A2 may be >0.5 micron, >1 micron, <15 micron, <5 micron or 1.5 micron

[0220] - The minimum characteristic particle size of the cathode active material may be greater than 0.5, >1, >2 or >5 microns, and the maximum characteristic particle size of the cathode may be less than 70, <50, <30, <20 or <15 microns

[0221] - The most common particle size of the solid polymer electrolyte component B1 can be <5 μm or >1.6 μm

[0222] - The most common particle size of the solid polymer electrolyte component B2 can be <1.5 μm, >0.35 μm or 0.7 μm

[0223] - The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron

[0224] - The maximum characteristic particle size of the solid polymer electrolyte can be >10 microns, >20 microns or <50 microns

[0225] - The particle size distribution of a subgroup can be approximated using a lognormal distribution function (including single or multiple components). Multiple components with lognormal distributions can be used to approximate component A and component B

[0226] -

[0227] -Where x is the particle size, μ is the average particle size, and σ is the standard deviation or dispersion

[0228] -component, the dispersion of A1 may be <0.5, <0.4, <0.3, <0.2 or <0.15

[0229] - component, the dispersion of A2 may be <0.5, <0.45, <0.4, <0.3, <0.25 or <0.15

[0230] - component, the dispersion of B can be <0.7, <0.65 or <0.6

[0231] - component, the dispersion of B1 may be <0.7, <0.6, <0.5, <0.4, <0.3 or <0.2

[0232] - component, the dispersion of B2 may be <0.9, <0.8, <0.7, <0.6, <0.5, <0.45 or <0.4

[0233] Cathode slurry coating process

[0234] In one example, the cathode slurry can be coated at a speed of 1 to 10 m / min using one of the coating methods described above (e.g., example procedures 1, 2, or 3). After coating, the electrode roller passes through a set of multiple ovens, in which drying conditions can be set to achieve an evaporation rate range of 30-200 g / min. The value of this range can be optimized to reduce the migration or spatial gradient of component D1 (binder), the network distribution of component B (solid ion conductive polymer material), the optimized uniformity of the coating weight on the coating width, and good coating adhesion (≥10 gf / in). The latter parameter can provide subsequent stamping of the electrode without compromising the integrity of the coating, and there is delamination on the surface or along the edge of the stamped electrode.

[0235] Characterization of the two-dimensional distribution of polymer electrolyte in the cathode

[0236] The two-dimensional distribution of component B was quantified by SEM-EDS images. Fig.10 In the illustrated SEM image 1000 , the surface of the cathode coating is shown, wherein component B is highlighted in white and the background is shown in black.

[0237] - Using nearest neighbor distance (NND) analysis, the 2D distribution of polymer electrolytes can be clustered with an average NND between 3-10 μm.

[0238] - The maximum Feret distance (the longest distance between two points on the boundary of a particle of component B) may be between 0.6 and 10 μm.

[0239] - The particle size can be between 0.2-23 μm 2 between.

[0240] - The circularity of the particles in the cathode, given by Defined, can be between 0.2-1.0.

[0241] anode

[0242] Similar to the discussion about the cathode, the anode layer can also utilize the disclosed process. In one example, the anode layer of the unit can include a variety of materials that can be characterized as powders in isolated groups, as long as a large number of particles with similar components and properties are included. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer having functionality derived from its composite onto a substrate, which in the case of the present invention can be a current collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, the methods by which the materials can be combined to form a slurry, the characteristics of the slurry, and the casting method of the slurry is provided.

[0243] In this example, the composite including the anode and its derived slurry can be formed from a combination of multiple materials with active and passive functions. During the steps required to complete the fabrication of the layer, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry casting.

[0244] Anodic compositions, in slurry or other form, may be defined as follows:

[0245] - Composition (total) = Component A + Component B + Component C + Component D

[0246] -wherein component A corresponds to the anode active material

[0247] -wherein component B corresponds to a conductive solid polymer

[0248] -where component C corresponds to the free volume

[0249] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0250] Thus, the anode slurry may include the following components:

[0251] Component A

[0252] - A combination of one or more active materials, such as graphite, silicon, silicon oxide, lithium metal, lithium titanium oxide, with a primary particle size between 0.01 and 20 μm or a foil thickness below 50 μm

[0253] Section B

[0254] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0255] Component C

[0256] Component D

[0257] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0258] -Component D2: electronic conductor, such as carbon black, super P, vapor-grown carbon fiber

[0259] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0260] - Component D4: one or more dispersing solvents, such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0261] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0262] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds resulting from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0263] In addition to the solvent, the anode slurry may contain the previous components within the following ranges:

[0264] - solid ion-conducting polymer material, between 0 and 10 wt.%

[0265] - Active material, between 85 and 95 wt.%

[0266] - Binder, content between 0.1 and 10 wt.%

[0267] -Electronic conductor, between 1 and 10 wt.%

[0268] - Surfactant, content between 0 and 5 wt.%

[0269] In this example, the composite volume of the anode layer can be defined as

[0270] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0271] - The volume percentage of component A may be >35%, >50%, >55%, >60%, or >70%. It should be noted that similar to the cathode example, these values ​​include porosity values ​​between 15% and 40% by volume.

[0272] - The volume percentage of component B may be <35%, <30%, <25%, <20%, or <15%

[0273] -The volume percentage of component C may be <40%, <30%, <20%, or <15%

[0274] - The volume percentage of component D may be <30%, <25%, <10%, or <5%

[0275] - The sum of the volume percentages of components C and D may be less than 40%, <30%, <20%, or <15%

[0276] The size of the particles, including the powder form of components A and B, can also be described by:

[0277] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0278] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0279] - In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for 100%, <95%, <85%, or <80%, and the remainder of component A, identified by A2, belongs to A 2,mean mean Groups of particles located in the spaces between larger particles

[0280] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0281] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0282] - In the volume % including component B, the size distribution is determined by the average value B 1,mean >B mean The particles of the group described in the form account for >80%, <85%, <90%, or <95%, and the remainder of component B, identified by B2, belongs to B 2,mean mean Groups of particles located in the spaces between larger particles

[0283] The relative fractions of component A and component B that make up the complex (total) can be described as follows:

[0284] - As the volume % (including percentage of total solid volume) of component A increases, the volume % of component B (including B2) will increase relative to the volume % of component B (including B1).

[0285] ​​- As the ratio of component A1 to component A2 decreases, the ratio of the volume % of component B (including B1) to the volume % of component B (including B2) may decrease.

[0286] - The fraction of component A added to the complex (total) in the form of A1 may be 100%, <95%, <90%, <85%, <80% or <75%

[0287] - The fraction of component B added to the complex (total) in the form of B1 may be 100%, <90%, <80%, <70%, <60% or <50%, 40%, <30%, <20%, or <15%

[0288] Before its coating, the negative electrode slurry can be characterized as:

[0289] - At 85 Hz, the viscosity is between 1100 and 2800 cps.

[0290] - Solids content between 40% and 65%

[0291] -Hegman gauge below 80μm or below 5μm

[0292] - Particle size distribution is as follows: d10 < 10 μm, d50 < 30 μm, d90 < 60 μm, d99 < 140 μm

[0293] Fig.11 A representative particle size distribution curve is shown in the graph 1100 of FIG. Table 2 provides the particle size distribution of the anode material coating slurry, and Fig.12 A representative viscosity curve is shown in graph 1200 of , where viscosity is inversely proportional to shear rate.

[0294] Table 2: Particle size distribution of slurry for anode material coating, as shown in graph 1100.

[0295] Distribution Percent Component A (anode) Representative anode slurry <![CDATA[D 10 ]]> 8.69 7.98 <![CDATA[D 50 ]]> 15.9 15.8 <![CDATA[D 90 ]]> 29.2 30.6 <![CDATA[D 99 ]]> 50.6 136

[0296] It should be understood that according to the above method, the calendering can be performed in a low humidity environment at a temperature between room temperature (20° C.) and 60° C. The thickness of the negative electrode after calendering can be between 100 and 400 μm.

[0297] Anode slurry mixing process

[0298] Example of anode slurry mixing process step 4: three-stage addition of component D1A

[0299] Component D1A may be added in steps ii, iii and vi.

[0300] i. Mixing speed and equipment

[0301] The dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor mixer or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0302] ■ Low shear shaft between 10 and 55 rpm

[0303] ■High shear shaft between 0 and 1500 rpm

[0304] ii. Solution of component D1 in component D4

[0305] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0306] iii. Dispersed component D2

[0307] A portion of the component D1A solution (5% to 30%) and component D2 may be mixed between 30 minutes and 90 minutes. After this step, the slurry may be characterized by a solids content between 1 and 25 wt.%.

[0308] iv. Dispersed component B

[0309] Another portion (30% to 70%) of the component B and component D1A solutions can be added to the previous slurry and mixed for between 30 and 90 minutes. After this step, the solids content can be between 5 and 30 wt.%.

[0310] v. Dispersed component A

[0311] Half of component A can be added to the mixing vessel to a solids content between 25 and 60 wt.%; the solution can be mixed for 45 to 120 minutes. The other half of component A can be added to the mixing vessel to a solids content between 40 and 70 wt.% and mixed for 120 minutes to 16 hours.

[0312] vi. Dispersed component D1B

[0313] Another portion (10% to 50%) of component D1A can be added to the previous slurry and mixed between 30 to 90 minutes to a solid content between 40 and 70 wt.%. Component D1B solution can be added to the slurry and mixed between 30 to 90 minutes. After this step, the slurry can be characterized by a solid content between 40 and 65 wt.% and a viscosity between 1100 and 2800 cps.

[0314] vii. Target solids percentage

[0315] Some additional solvent may be added at this point to adjust the final slurry properties.The slurry may be mixed under vacuum for 30 to 120 minutes.

[0316] Example of anode slurry mixing process step 5: two-stage addition of component D1A

[0317] Component D1A may be added in steps ii and v.

[0318] vi. Mixing speed and equipment

[0319] The dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor mixer or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0320] ■ Low shear shaft between 10 and 55 rpm

[0321] ■High shear shaft between 0 and 1500 rpm

[0322] vii. Solution of component D1 in component D4

[0323] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0324] viii. Dispersed component D2

[0325] A portion (between 50% and 85%) of component D1A and component D2B may be mixed between 30 and 90 minutes. After this step, the solids content may be between 1 and 25 wt.%.

[0326] ix. Dispersed component B

[0327] Component B can be added to the previous slurry and mixed for between 30 and 90 minutes. After this step, the solids content can be between 5 and 30 wt.%.

[0328] x, Dispersed component A

[0329] Half of component A can be added to a mixing vessel; the solution can be mixed for 45 to 120 minutes. After this step, the solids content is between 25 and 60 wt.%. The other half of component A and a portion of the component D1A solution (15% to 50%) can be added to a mixing vessel and mixed for 120 minutes to 16 hours. After this step, the slurry characteristics can include a solids content between 40 and 70 wt.%.

[0330] xi. Dispersed component D1B

[0331] The component D1B solution may be added to the slurry and mixed for between 30 and 90 minutes.

[0332] xi. Target solid percentage

[0333] Some additional solvent may be added at this point to adjust the final slurry properties. The slurry may be mixed under vacuum for 30 minutes to 120 minutes. The final slurry properties may look like this:

[0334] -d10<15μm, d50<30μm, d90<60μm, d99<100μm

[0335] -Hegman gauge <80μm

[0336] - Solid content between 40 and 65 wt.%

[0337] -Viscosity between 1100 and 2800 cps at 85 Hz

[0338] Example of anode slurry mixing process step 6: single-stage addition of main components A and B

[0339] i. Mixing speed and equipment

[0340] Dispersion of the components can be achieved by a single shaft mixer equipped with a sawtooth high speed disperser. The high shear shaft mixing speed can be maintained between 500 and 1200 rpm throughout the mixing process.

[0341] ii. Solution of component D1 in component D4

[0342] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0343] iii. Dispersed components D2, B and A

[0344] Component D2 can be dispersed into a portion of the component D1A solution along with component B and all of component A for 90-120 minutes. The solids content of the slurry in this step can be 40-60%.

[0345] iv. Dispersed component D1B

[0346] Next, the slurry can be diluted with the remainder of the component D1A solution for 60-90 minutes. Finally, the component D1B solution can be mixed into the slurry for 60-90 minutes. The final solids content can be between 45-50%.

[0347] Fig.13A process flow diagram depicting step 6 of the anode slurry mixing process.

[0348] Example of anode slurry mixing process step 7: single-stage addition of main component A

[0349] i. Mixing speed and equipment

[0350] Dispersion of the components can be achieved by a single shaft mixer equipped with a sawtooth high speed disperser. The high shear shaft mixing speed can be maintained between 500 and 1200 rpm throughout the mixing process.

[0351] ii. Solution of component D1 in component D4

[0352] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0353] iii. Dispersed components D2 and D3

[0354] Component D2 and component D3 can be dispersed into the component D1A solution. The solid content in this step can be 1-15%.

[0355] iv. Dispersed component B

[0356] Component B may be added and mixed for 30-90 minutes. The solids content in this step may be 5-30%.

[0357] v. Dispersed component A

[0358] Next, all components A can be dispersed into the slurry for 90-120 minutes. The solid content in this step can be 40-70%.

[0359] vi. Dispersed component D1B

[0360] Finally, the component D1B solution can be mixed into the slurry for 30-60 minutes. The solid content in this step can be 45-65%.

[0361] Fig.14 A process flow diagram of an example step 7 of an anode slurry mixing process is depicted in FIG.

[0362] Example of anode slurry mixing process step 8: Four-stage addition of component D1A

[0363] i. Mixing speed and equipment

[0364] The dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor mixer or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0365] ■ Low shear shaft between 10 and 55 rpm

[0366] ■High shear shaft between 0 and 1500 rpm

[0367] ii. Solution of component D1 in component D4

[0368] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0369] iii. Dispersed components D2 and B

[0370] A portion of the component D1 solution (between 55 and 90%), component D2 and component B may be mixed for between 60 and 180 minutes. After this step, the solids content may be between 5 and 20 wt.%.

[0371] iv. Dispersed component A

[0372] Half of component A can be added to the mixing vessel; the solution can be mixed for 60 to 240 minutes. After this step, the slurry characteristics include a solids content between 25 and 55 wt.%. The other half of component A can be added to the slurry. 10% to 45% of the component D1A solution can be added at this time. The slurry can be mixed for 120 minutes to 16 hours. After this step, the solids content can be between 40 and 75 wt.%.

[0373] v. The remainder of the dispersed component D1A

[0374] At this point 10% to 45% of the component D1A solution may be added. The slurry may be mixed for between 30 and 60 minutes. After this step, the solids content may be between 40 and 70 wt.%.

[0375] vi. Dispersed component D1B

[0376] The component D1B solution and the remaining component D1A solution can be added to the slurry. During this step, some solvent can also be added to adjust the slurry viscosity. The slurry can be mixed between 30 minutes and 16 hours.

[0377] vii. Target solids percentage

[0378] At this point, some additional solvent may be added to adjust the final slurry properties. The slurry may be mixed under vacuum for 30 to 120 minutes. The final slurry properties may be as follows:

[0379] -d10<15μm, d50<30μm, d90<60μm, d99<100μm

[0380] -Hegman gauge <80μm

[0381] - Solids content between 40 and 65% by weight

[0382] -Viscosity between 1100 and 2800 cps at 85 GHz

[0383] Table 3 provides an example of the process of mixing the anode slurry with graphite (anode active material).

[0384] Table 3: Example of anode slurry and graphite (anode active material) mixing process.

[0385]

[0386]

[0387] An alternative method to mixing is also provided to distribute the solid electrolyte components.

[0388] For example, to facilitate the distribution of component particles, provide optimal density and maintain the functionality of the component materials, the order in which the particle groups of different materials are added to the mixture is carefully selected. Smaller particles have a tendency to be interspersed among larger particles. To achieve this effectively, the uniformity of the distribution of larger particles must first be determined. In addition, in order to obtain higher gravimetric analysis capabilities, the total content of each component material can be divided into several groups to design the distribution of large particle groups relative to smaller particle groups.

[0389] Given the previous definition of the composite volume of the cathode layer, it is defined as:

[0390] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0391] -wherein component A corresponds to the cathode active material

[0392] -wherein component B corresponds to an ion-conducting solid polymer

[0393] -where component C corresponds to the free volume

[0394] -where component D corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[0395] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0396] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0397] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0398] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0399] Taking into account the above design criteria, the order in which the components of the cathode layer are combined by a mixing process to form a mixture of components A, B, C and D is specified as follows:

[0400] Step 1, initially, component A1 can be mixed with a portion of component B2

[0401] Step 2, component A1 can be mixed with a portion of component D to provide a dispersed group of A1 particles decorated with B1 particles.

[0402] Step 3, alone or in combination with component A1, components B1 and A2 may be mixed together with a further portion of component D

[0403] Step 4, a portion of component B2 can be added to the mixture

[0404] Step 5, component B2 and the remaining portion of component D may be gradually added to the mixture until the mixture may include all of components A1, A2, B1, B2 and D.

[0405] In addition to the above, the use of a discontinuous binder medium is considered part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without inhibiting the transfer of charged species at the interface between the active material of the electrode and the ion-conductive particles dispersed throughout the battery layer or between the polymer solid particles forming the electrolyte layer.

[0406] To deploy this strategy, staged mixing is again utilized, whereby the active material for a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid electrolyte. This ion-conductive powder-coated active material can then be mixed with a binder carrier that is resistant to dissolving agents in the slurry solvent. After mixing the solid electrolyte-coated active material and the non-soluble binder carrier, an additional soluble binder component can be added to adjust the mechanical durability of the electrode without compromising the ion-conducting and electroactive material functionality.

[0407] An example of this process can be described as follows:

[0408] Step 1, initially, component A1 can be mixed with a portion of component B2

[0409] Step 2: The mixture of component A1 and component B2 can be mixed with component D 1A (insoluble binder) and a portion thereof, provided with B2 particles and D 1A (Insoluble Binder) Particle Decorated Dispersed A1 Particle Group

[0410] Step 3, a portion of B1 and component D 1B (soluble binder) is added to the mixture of component A1, component B2 and component D1 (insoluble binder)

[0411] Step 4: Components B1 and A2 may be prepared alone or in combination with components A1, B2 and D. 1A (insoluble) mixture, and further add component D 1B (Soluble adhesive) part

[0412] Step 5, a portion of component B2 can be added to the mixture

[0413] Step 6, Component B2 and Component D 1B The remainder of the mixture may be gradually added to the mixture until the mixture may include components A1, A2, B1, B2, D 1A and D 1B All

[0414] To promote the desired distribution of the above components, the following parameters can be used when using this method to guide the optimization of the component particle size distribution:

[0415] The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4.

[0416] - The most common particle size of cathode active material component A1 can be less than 20 microns, greater than 5 microns or 10 microns

[0417] - The most common particle size of cathode active material component A2 may be >0.5 micron, >1 micron, <15 micron, <5 micron or 1.5 micron

[0418] - The minimum characteristic particle size of the cathode active material may be greater than 0.5, >1, >2 or >5 microns, and the maximum characteristic particle size of the cathode may be less than 70, <50, <30, <20 or <15 microns

[0419] - The most common particle size of the solid polymer electrolyte component B1 can be <5 μm or >1.6 μm

[0420] - The most common particle size of the solid polymer electrolyte component B2 can be <1.5 μm, >0.35 μm or 0.7 μm

[0421] - The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron

[0422] - The maximum characteristic particle size of the solid polymer electrolyte can be >10 microns, >20 microns or <50 microns

[0423] - The particle size distribution of a subgroup can be approximated using a lognormal distribution function (including single or multiple components). Multiple components with lognormal distributions can be used to approximate component A and component B

[0424] -

[0425] -Where x is the particle size, μ is the average particle size, and σ is the standard deviation or dispersion

[0426] - The dispersion degree of component A1 may be <0.5, <0.4, <0.3, <0.2 or <0.15

[0427] - The dispersion degree of component A2 may be <0.5, <0.45, <0.4, <0.3, <0.25 or <0.15

[0428] - The dispersion of component B can be <0.7, <0.65 or <0.6

[0429] - The dispersion degree of component B1 may be <0.7, <0.6, <0.5, <0.4, <0.3 or <0.2

[0430] - The dispersion degree of component B2 may be <0.9, <0.8, <0.7, <0.6, <0.5, <0.45 or <0.4

[0431] Anode slurry coating process

[0432] In one example, the anode slurry can be coated at a speed of 1 to 10 m / min using one of the coating methods described above (e.g., example procedures 4, 5, 6, 7, or 8). After coating, the electrode roller passes through a set of multiple ovens, in which drying conditions can be set to achieve an evaporation rate range of 30-150 g / min. The values ​​of this range can be optimized to reduce the migration or spatial gradient of component D1 (binder), the network distribution of component B (solid ion conductive polymer material), the optimized uniformity of the coating weight over the coating width, and good coating adhesion (≥10 gf / in). The latter parameter may be important for the subsequent stamping of the electrode, without affecting the integrity of the coating, and delamination will occur on the surface or along the edge of the stamped electrode.

[0433] Interface cathode-spacer layer

[0434] In another example, the interfacial cathode spacer layer of the cell may include a variety of materials that can be characterized as powders in an isolated population, as long as a large number of particles with similar composition and properties are included. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer having functionality derived from its composite onto a substrate, which in the case of the present invention can be a current collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, the methods by which the materials can be combined to form a slurry, the characteristics of the slurry, and the casting method of the slurry is provided.

[0435] In one example, the composite including the interfacial cathode spacer layer and its derived slurry can be formed from a combination of multiple materials with active and passive functions. During the steps required to complete the fabrication of the layer, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry coating.

[0436] The slurry used to apply the interface layer between the cathode layer and the spacer layer must include one or more solid ion-conducting polymer materials as the primary ion-conducting medium and the cathode active material as the primary energy storage medium. The primary particle size of the solid ion-conducting polymer material can be between 0.01 and 20 μm.

[0437] In one example, the composition (paste or other form) of the interfacial cathode spacer layer may be defined as follows:

[0438] - Composition (total) = Component A + Component B + Component C + Component D

[0439] -wherein component A corresponds to the cathode active material

[0440] -wherein component B corresponds to an ion-conducting solid polymer

[0441] -where component C corresponds to the free volume

[0442] -where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional components

[0443] Thus, the interfacial cathode spacer layer slurry may include the following components:

[0444] Component A

[0445] - A combination of one or more active materials, for example one or more of the following active materials: lithium iron phosphate (LFP), spinel LNMO, LiCoPO4, LiNiPO4, LVP, LVPF, LiNixMnyCozO2 or LiNixCoAlZO2, with a primary particle size between 0.01 and 20 μm

[0446] Component B

[0447] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0448] Component C

[0449] Component D

[0450] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0451] -Component D2: electronic conductor, such as carbon black, super P, vapor-grown carbon fiber

[0452] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0453] - Component D4: one or more dispersing solvents, such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0454] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0455] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0456] - Component D7: one or more lithium salts, including Li + Cations such as LiClO4, LiAsF6, LiF6, LiF4, LiRFSO3, LiC3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonyl), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide)

[0457] - Component D8: one or more additives for reducing interfacial impedance, such as urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyether and alkylurethane; l-methyl-3-pyrrolidone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(lH)-pyrimidinone; l,5-dimethyl-2-pyrrolidone; alkyl-substituted pyridyl ionic liquids, alkyl-substituted pyrrolidinyl ionic liquids and alkyl-substituted ammonium ionic liquids with counter anions, such as TFSI, PF6, BF4 anions; substituted polyethylene glycols with functional end groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic) or nitriles; polyethylene glycol bis(carboxymethyl) ether; dioctyl sulfosuccinate sodium, lithium or potassium salt; glycolic acid ethoxylated 4-tert-butylphenyl ether; glycolic acid ethoxylated lauryl ether; glycolic acid ethoxylated 4-nonylphenyl ether; glycolic acid ethoxylated oleyl ether; poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium or potassium salt; and sodium, lithium or potassium dodecylbenzenesulfonate.

[0458] In this example, in addition to the solvent, the interface layer slurry between the cathode layer and the spacer layer may include the previous components within the following ranges:

[0459] - solid ion-conducting polymer material, between 12 and 45 wt.%

[0460] - Active material, between 50 and 85 wt.%

[0461] - Binder, content between 0.1 and 10 wt.%

[0462] -Electronic conductor, between 1 and 10 wt.%

[0463] - Surfactant, content between 0 and 5 wt.%

[0464] In some examples, the composite volume of the cathode-separator interface layer may be defined as

[0465] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0466] - The volume percentage of component A may be >15%, >30%, >45%, >50%, >55%, or >60%

[0467] - The volume percentage of component B may be 70%, <60%, <50%, <45%, <40%, <35%, <30%, or <25%

[0468] - The volume percentage of component C may be <40%, <30%, <20%, or <15%

[0469] - The volume percentage of component D may be <30%, <25%, <10%, or <5%

[0470] - The sum of the volume percentages of components C and D may be less than 40%, <30%, <20%, or <15%

[0471] The size of the particles, including the powder form of components A and B, can also be described by:

[0472] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0473] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than Amean Size distribution

[0474] - In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for <20%, <15%, <10%, or <5%, and the remainder of component A, identified by A2, belongs to A 2,mean mean Group

[0475] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0476] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0477] - In the volume % including component B, the size distribution is determined by the average value B 1,mean >B mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component B, identified by B2, belongs to B 2,mean mean Groups of particles located in the spaces between larger particles

[0478] For example, the relative fractions of component A and component B that make up the complex (total) can be described as follows:

[0479] - The fraction of component A added to the complex (total) in the form of A1 may be 25%, <20%, <15%, <10%, <5%

[0480] - The fraction of component B added to the complex (total) in the form of B1 may be >35%, >45%, >55%, >65%, >75%, >85%

[0481] Prior to its coating, the cathode-spacer interface slurry can be characterized as:

[0482] - Viscosity between 500 and 2600 cps at 85 Hz, measured by parallel plate rheometer.

[0483] - Solids content between 40% and 75%

[0484] ​​-Hegman gauge below 90μm or below 5μm

[0485] - Particle size distribution is as follows: d10 < 10 μm, d50 < 30 μm, d90 < 60 μm, d99 < 100 μm

[0486] The thickness of the positive electrode including the interfacial cathode separator interfacial layer after calendering may be between 105 and 450 μm. Calendering may be performed in a low humidity environment between room temperature (20° C.) and 140° C.

[0487] Cathode-separator interface layer slurry mixing process

[0488] Some example processes are described below.

[0489] Example of cathode-spacer interface slurry mixing process Step 9: Adding component D1 (binder) as solution in multiple stages

[0490] i. Mixing speed and equipment

[0491] The dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor mixer or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0492] ■ Low shear shaft between 10 and 55 rpm

[0493] ■High shear shaft between 0 and 1500 rpm

[0494] ii. Solution of component D1 in component D4

[0495] First, component D1 can be dissolved in component D4 to form 1 and 15 wt. % solutions.

[0496] iii. Dispersed component D2

[0497] A portion of the component D1 solution (10% to 60%) and component D2 can be mixed between 30 minutes and 90 minutes. After this step, the solids content is between 5 and 30 wt.%.

[0498] iv. Dispersed component B

[0499] Then, another portion (5% to 40%) of the component B and component D1 solutions can be added to the previous suspension and mixed for between 30 and 90 minutes. After this step, the solids content can be between 10 and 50 wt.%.

[0500] v. Dispersed component A

[0501] Half of component A can be added to a mixing container along with another portion of component D1 solution (10% to 70%); the solution can be mixed for another 45 to 120 minutes. After this step, the solids content can be between 40 and 80 wt.%. The other half of component A and the remainder of component D1 solution can be added to a mixing container and mixed for 120 minutes to 16 hours.

[0502] vi. Target solid percentage

[0503] Some additional component D4 may be added at this point to achieve the final slurry properties as described above in the options provided for component D4. After this step, the slurry properties should be:

[0504] ■d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0505] ■Hegman gauge <50μm

[0506] ■Solid content between 40-80wt.%

[0507] ■Viscosity between 2000 and 2600 cps at 85 Hz

[0508] The process flow diagram 900 of the exemplary process step 9 is as follows: Fig. 9 shown.

[0509] Example Procedure 10 of Cathode Spacer Interface Slurry Mixing Process: Add binder in powder form in a single stage.

[0510] i. Mixing speed and equipment

[0511] Dispersion of the components can be achieved by a combination of single-shaft mixers equipped with sawtooth high shear dispersers and multi-shaft mixers equipped with multiple high shear dispersers, low shear anchor mixers or low shear helical impellers.

[0512] Throughout the mixing process, the mixing speed can be maintained as follows:

[0513] ■ Low shear shaft between 10 and 55 rpm

[0514] ■High shear shaft between 0 and 1500 rpm

[0515] ii. Dispersed component D2

[0516] Component D4, component D1 and component D2 may be mixed for between 30 and 90 minutes. After this step, the solids content may be between 5 and 30 wt.%.

[0517] iii. Dispersed component B

[0518] Component B and more component D4 can be added to the previous suspension and mixed for between 30 and 90 minutes. After this step, the slurry solids content can be between 10 and 50 wt.%.

[0519] iv. Dispersed component A

[0520] Half of component A can be added to the mixing vessel along with more component D4. The solution can be mixed for another 45 to 120 minutes. After this step, the slurry solids content can be between 40 and 80 wt.%. The other half of component A and more component D4 can be added to the mixing vessel and mixed for 120 minutes to 16 hours.

[0521] v. Target solid percentage

[0522] Additional solvent may be added at this point to achieve the final slurry properties described above. After this step, the slurry properties may be:

[0523] ■d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0524] ■Hegman gauge <50μm

[0525] ■Solid content between 40-80wt.%

[0526] ■At 85Hz, the viscosity is between 1000 and 2000cps

[0527] Example of cathode-separator interface slurry mixing process Procedure 11: Mixing using only high shear disperser.

[0528] i. Mixing speed and equipment

[0529] The dispersion of the components can be achieved using a single shaft mixer equipped with a sawtooth high speed disperser. The high shear shaft mixing speed can be maintained between 0 and 1500 rpm throughout the mixing process.

[0530] ii. Solution of component D1 in component D4

[0531] First, component D1 can be dissolved in component D4 to form 1 and 15 wt. % solutions.

[0532] iii. Dispersed component D2

[0533] Component D1 in D4 solution can be used, wherein component D2A from the options provided above for component D2 can be dispersed first. Mixing can be for 30-90 minutes. Next, the second component (component D2B) from the options provided above for component D2 can be dispersed for another 30-90 minutes. The solid content is about 10%.

[0534] iv. Dispersed component B

[0535] Next, component B can be dispersed into the slurry for 30-90 minutes. After this step, component A can be added in its entirety, wherein the slurry can be mixed for 2-12 hours.

[0536] v. Target solid percentage

[0537] Finally, component D4 may be added to adjust the solids content of the slurry to between 50-60%.

[0538] An alternative method of mixing the solid electrolyte components is also provided.

[0539] In other examples, as described above, in order to facilitate the distribution of the component particles, provide optimal density and maintain the functionality of the component materials, the order in which the particle groups of different materials are added to the mixture must be carefully selected. Smaller particles tend to be interspersed between larger particles. In order to achieve this effectively, the uniformity of the distribution of larger particles must first be determined. In addition, in order to obtain the highest possible gravimetric analysis capability, the total content of each component material can be divided into several groups to design the distribution of large particle groups relative to smaller particle groups.

[0540] In view of the composite volume of the cathode-separator layer, it can be defined as:

[0541] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0542] -wherein component A corresponds to the cathode active material

[0543] -wherein component B corresponds to an ion-conducting solid polymer

[0544] -where component C corresponds to the free volume

[0545] -where component D corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[0546] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0547] - In the volume percentage including component A, it can be assigned an average particle size value A mean, the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0548] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0549] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0550] Taking into account the above-mentioned design criteria, the order in which the components of the cathode-separator layer are combined by a mixing process to form a mixture of components A, B, C and D is specified as follows:

[0551] Step 1, components A2 and B1 can be combined in a stepwise manner and can be mixed with a portion of component D to provide a dispersed group

[0552] Step 2, a portion of component B2 can be added to the mixture by further adding a portion of component D

[0553] Step 3, component B2 and the remaining portion of component D may be gradually added to the mixture until the mixture may include the sum of components A2, B1, B2 and D.

[0554] Likewise, as described above, the above-described strategy of using a discontinuous binder medium is considered part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without inhibiting the transfer of charged species at the interface between the active material of the electrode and the ion-conductive particles dispersed throughout the battery layer or between the polymer solid particles forming the spacer layer. In order to deploy this strategy, staged mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid electrolyte. This ion-conductive powder-coated active material can then be mixed with a binder carrier that is resistant to dissolving agents in the slurry solvent. After mixing the solid electrolyte-coated active material and the non-soluble binder carrier, an additional soluble binder component can be added to adjust the mechanical durability of the electrode without compromising the functionality of the ion-conductive and electroactive materials.

[0555] For example, one version of this process could be described as follows:

[0556] Step 1, components A2 and B1 can be combined in a stepwise manner and can be mixed with a portion of component D to provide a dispersed group

[0557] Step 2, the mixture of components A2 and B1 can be mixed with component D1A (insoluble binder) to provide A2, B1 and D 1A Dispersion of particles

[0558] Step 3, a portion of component B2 can be mixed with component D1B (soluble binder) is added to the mixture together

[0559] Step 4, Component B2 and Component D 1B The remainder of the (soluble binder) may be gradually added to the mixture until the mixture may include all of components A2, B1, B2 and D.

[0560] Similar to the above description, in order to promote the expected distribution of the above components, the following parameters can be applied to guide the method of optimizing the particle size distribution of the components:

[0561] The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4.

[0562] - The most common particle size of cathode active material component A1 can be less than 20 microns, greater than 5 microns or 10 microns

[0563] - The most common particle size of cathode active material component A2 may be >0.5 micron, >1 micron, <15 micron, <5 micron or 1.5 micron

[0564] - The minimum characteristic particle size of the cathode active material may be greater than 0.5, >1, >2 or >5 microns, and the maximum characteristic particle size of the cathode may be less than 70, <50, <30, <20 or <15 microns

[0565] - The most common particle size of the solid polymer electrolyte component B1 can be <5 μm or >1.6 μm

[0566] - The most common particle size of the solid polymer electrolyte component B2 can be <1.5 μm, >0.35 μm or 0.7 μm

[0567] - The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron

[0568] - The maximum characteristic particle size of the solid polymer electrolyte can be >10 microns, >20 microns or <50 microns

[0569] - The particle size distribution of a subgroup can be approximated using a lognormal distribution function (including single or multiple components). Multiple components with lognormal distributions can be used to approximate component A and component B

[0570] -

[0571] -Where x is the particle size, μ is the average particle size, and σ is the standard deviation or dispersion

[0572] - The dispersion degree of component A1 may be <0.5, <0.4, <0.3, <0.2 or <0.15

[0573] - The dispersion degree of component A2 may be <0.5, <0.45, <0.4, <0.3, <0.25 or <0.15

[0574] - The dispersion of component B can be <0.7, <0.65 or <0.6

[0575] - The dispersion degree of component B1 may be <0.7, <0.6, <0.5, <0.4, <0.3 or <0.2

[0576] - The dispersion degree of component B2 may be <0.9, <0.8, <0.7, <0.6, <0.5, <0.45 or <0.4

[0577] Cathode spacer interface layer slurry coating process

[0578] In one example, the cathode spacer interface layer can be coated, cast, deposited or laid on the positive electrode, the negative electrode or both electrodes to ensure a high degree of consistency between the spacer and the electrodes. The coating process can be performed according to the following configurations:

[0579] - The anode and cathode are coated with the same separator formulation,

[0580] - coating the anode with two different separators in a formulation to optimize the chemical and electrochemical stability between each electrode and separator,

[0581] - Coating a series of layers of different formulations on the anode and / or cathode to allow for a gradient in the composition of the separator, thereby enhancing the chemical and electrochemical stability of the electrode with the separator.

[0582] In order to ensure continuous coverage of the electrode to be coated with the spacer layer, the width of the two coating layers can be the same. The width of the spacer layer can also be slightly larger than the coating width of the supporting electrode.

[0583] The cathode spacer interface layer slurry can be coated at a speed of 1 to 10 m / min using one of the coating methods described above (e.g., example procedures 9, 10, or 11). After coating, the electrode roller passes through a set of multiple ovens, in which drying conditions can be set to achieve an evaporation rate range of 30-200 g / min. The values ​​of this range can be optimized to reduce the migration or spatial gradient of component D1 (binder), the network distribution of component B (solid ion conductive polymer material), the optimized uniformity of the coating weight over the coating width, and good coating adhesion (≥10 gf / in). The latter parameter can provide subsequent stamping of the electrode without compromising the integrity of the coating, and delamination will occur on the surface or along the edge of the stamped electrode.

[0584] Interface anode-spacer layer

[0585] In one example, the interfacial anode-spacer layer of the cell may include a variety of materials that may be characterized as powders in an isolated population, provided that a large number of particles having similar composition and properties are included. These powders may be combined with other materials to form a slurry to facilitate deposition of a continuous layer having functionality derived from its composite onto a substrate, which in the case of the present invention may be a current collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, methods by which the materials may be combined to form a slurry, characteristics of the slurry, and methods of casting the slurry is provided.

[0586] Composites including interfacial anode-spacer layers and derived slurries thereof can be formed from a combination of materials with active and passive functions. During the steps required to complete the fabrication of the layers, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry coating.

[0587] The slurry used to apply the interface layer between the anode layer and the spacer layer must include one or more solid ion-conducting polymer materials as the primary ion-conducting medium and the anode active material as the primary energy storage medium. The primary particle size of the solid ion-conducting polymer material can be between 0.01 and 20 μm.

[0588] The composite (paste or other form) of the interfacial anode spacer layer may be defined as follows:

[0589] - Composition (total) = Component A + Component B + Component C + Component D

[0590] -wherein component A corresponds to the anode active material

[0591] -wherein component B corresponds to an ion-conducting solid polymer

[0592] -where component C corresponds to the free volume

[0593] -where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional components

[0594] Thus, the interfacial anode spacer layer slurry may include the following components:

[0595] Component A

[0596] - A combination of one or more active materials, such as graphite, silicon, silicon oxide, lithium metal, lithium titanium oxide, with a primary particle size between 0.01 and 20 μm, or a foil thickness of less than 50 μm

[0597] Component B

[0598] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0599] Component C

[0600] Component D

[0601] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0602] -Component D2: electronic conductor, such as carbon black, super P, vapor-grown carbon fiber

[0603] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0604] - Component D4: one or more dispersing solvents, such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0605] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0606] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0607] - Component D7: one or more lithium salts, including Li + Cations such as LiClO4, LiAsF6, LiF6, LiF4, LiRFSO3, LiC3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonyl), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide)

[0608] - Component D8: one or more additives for reducing interfacial impedance, such as urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyether and alkylurethane; l-methyl-3-pyrrolidone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(lH)-pyrimidinone; l,5-dimethyl-2-pyrrolidone; alkyl-substituted pyridyl ionic liquids, alkyl-substituted pyrrolidinyl ionic liquids and alkyl-substituted ammonium ionic liquids with counter anions, such as TFSI, PF6, BF4 anions; substituted polyethylene glycols with functional end groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic) or nitriles; polyethylene glycol bis(carboxymethyl) ether; dioctyl sulfosuccinate sodium, lithium or potassium salt; glycolic acid ethoxylated 4-tert-butylphenyl ether; glycolic acid ethoxylated lauryl ether; glycolic acid ethoxylated 4-nonylphenyl ether; glycolic acid ethoxylated oleyl ether; poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium or potassium salt; and sodium, lithium or potassium dodecylbenzenesulfonate.

[0609] In addition to the solvent, the interface layer slurry between the anode layer and the spacer layer should contain the previous components within the following ranges:

[0610] - solid ion-conducting polymer material, between 10 and 70 wt.%

[0611] - Active materials, between 30 and 85 wt.%

[0612] - Binder, content between 0.1 and 10 wt.%

[0613] -Electronic conductor, between 1 and 10 wt.%

[0614] - Surfactant, content between 0 and 5 wt.% The composite volume of the anode-separator interface layer can be defined as

[0615] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0616] - The volume percentage of component A may be >10%, >20%, >30%, >40%, >50%, or >60%

[0617] - The volume percentage of component B can be <85%, <75%, <65%, <55%, <45%, <35%, or <30%

[0618] - The volume percentage of component C may be <40%, <30%, <20%, or <15%

[0619] - The volume percentage of component D may be <30%, <25%, <10%, or <5%

[0620] - The sum of the volume percentages of components C and D may be less than 40%, <30%, <20%, or <15%

[0621] The size of the particles, including the powder form of components A and B, can also be described by:

[0622] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0623] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0624] - In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for <20%, <15%, <10%, or <5%, and the remainder of component A, identified by A2, belongs to A 2,mean mean Group

[0625] - In the volume % comprising component B, it may be assigned an average particle size value B​mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0626] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0627] - In the volume % including component B, the size distribution is determined by the average value B 1,mean >B mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component B, identified by B2, belongs to B 2,mean mean A group of particles located in the spaces between larger particles

[0628] The relative fractions of component A and component B that make up the complex (total) can be described as follows:

[0629] - The fraction of component A added to the complex (total) in the form of A1 may be 25%, <20%, <15%, <10%, <5%

[0630] - The fraction of component B added to the complex (total) in the form of B1 may be >35%, >45%, >55%, >65%, >75%, >85%

[0631] Prior to its coating, the anode-spacer interface slurry can be characterized as:

[0632] -Viscosity between 500 and 2600 cps at 85 Hz

[0633] - Solids content between 40% and 75%

[0634] -Hegman gauge below 90μm or below 5μm

[0635] - Particle size distribution is as follows: d10 < 10 μm, d50 < 30 μm, d90 < 60 μm, d99 < 100 μm

[0636] In this example, the positive electrode thickness including the interfacial anode-separator interface layer after calendaring may be between 105 and 450 μm.

[0637] Anode-spacer interface slurry mixing process

[0638] An example procedure for forming the anode spacer interface slurry is provided below.​

[0639] Example of anode-spacer interface slurry mixing process step 12: three-stage addition of component D1A

[0640] Component D1A may be added in steps ii, iii and vi.

[0641] i. Mixing speed and equipment

[0642] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor agitator or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0643] ■ Low shear shaft between 10 and 55 rpm

[0644] ■High shear shaft between 0 and 1500 rpm

[0645] ii. Solution of component D1 in component D4

[0646] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0647] iii. Dispersed component D2

[0648] A portion of the component D1A solution (5% to 30%) and component D2 may be mixed between 30 minutes and 90 minutes. After this step, the slurry may be characterized by a solids content between 1 and 25 wt.%.

[0649] iv. Dispersed component B

[0650] Another portion (30% to 70%) of the component B and component D1A solutions can be added to the previous slurry and mixed for between 30 and 90 minutes. After this step, the solids content can be between 5 and 30 wt.%.

[0651] v. Dispersed component A

[0652] Half of component A can be added to the mixing vessel to a solids content between 25 and 60 wt.%; the solution can be mixed for 45 to 120 minutes. The other half of component A can be added to the mixing vessel to a solids content between 40 and 70 wt.% and mixed for 120 minutes to 16 hours.

[0653] vi. Dispersed component D1B

[0654] Another portion (10% to 50%) of component D1A can be added to the previous slurry and mixed between 30 to 90 minutes to a solid content between 40 and 70 wt.%. Component D1B solution can be added to the slurry and mixed between 30 to 90 minutes. After this step, the slurry can be characterized by a solid content between 40 and 65 wt.% and a viscosity between 1100 and 2800 cps.

[0655] vii. Target solids percentage

[0656] Some additional solvent may be added at this point to adjust the final slurry properties.The slurry may be mixed under vacuum for 30 to 120 minutes.

[0657] Example of anode-spacer interface slurry mixing process step 13: two-stage addition of component D1A

[0658] Component D1A may be added in steps ii and v.

[0659] i. Mixing speed and equipment

[0660] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor agitator or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0661] ■ Low shear shaft between 10 and 55 rpm

[0662] ■High shear shaft between 0 and 1500 rpm

[0663] ii. Solution of component D1 in component D4

[0664] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0665] iii. Dispersed component D2

[0666] A portion (between 50% and 85%) of component D1A and component D2B may be mixed between 30 and 90 minutes. After this step, the solids content may be between 1 and 25 wt.%.

[0667] iv. Dispersed component B

[0668] Component B can be added to the previous slurry and mixed for between 30 and 90 minutes. After this step, the solids content can be between 5 and 30 wt.%.

[0669] v. Dispersed component A

[0670] Half of component A can be added to a mixing vessel; the solution can be mixed for 45 to 120 minutes. After this step, the solid content is between 25 and 60 wt.%. The other half of component A and a portion of the component D1A solution (15% to 50%) can be added to a mixing vessel and mixed for 120 minutes to 16 hours. After this step, the slurry characteristics can include a solid content between 40 and 70 wt.%.

[0671] vi. Dispersed component D1B

[0672] The component D1B solution may be added to the slurry and mixed for between 30 and 90 minutes.

[0673] viii. Target solids percentage

[0674] Some additional solvent may be added at this point to adjust the final slurry properties. The slurry may be mixed under vacuum for 30 to 120 minutes. The final slurry properties may be as follows:

[0675] -d10<15μm, d50<30μm, d90<60μm, d99<100μm

[0676] -Hegman gauge <80μm

[0677] - Solids content between 40 and 65 wt%

[0678] -Viscosity between 1100 and 2800 cps at 85 Hz

[0679] Example of anode-spacer interface slurry mixing process step 14: single-stage addition of main components A and B i. Mixing speed Degrees and Equipment

[0680] Dispersion of the components can be achieved by a single shaft mixer equipped with a sawtooth high speed disperser. The high shear shaft mixing speed can be maintained between 500 and 1200 rpm throughout the mixing process.

[0681] ii. Solution of component D1 in component D4

[0682] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0683] iii. Dispersed components D2, B and A

[0684] Component D2 can be dispersed into a portion of the component D1A solution along with component B and all of component A for 90-120 minutes. The solids content of the slurry in this step can be 40-60%.

[0685] iv. Dispersed component D1B

[0686] Next, the slurry can be diluted with the remainder of the component D1A solution for 60-90 minutes. Finally, the component D1B solution can be mixed into the slurry for 60-90 minutes. The final solids content can be between 45-50%.

[0687] Example Procedure 15 for Anode Spacer Interface Slurry Mixing Process: Single-stage Addition of Primary Component A

[0688] i. Mixing speed and equipment

[0689] Dispersion of the components can be achieved by a single shaft mixer equipped with a sawtooth high speed disperser. The high shear shaft mixing speed can be maintained between 500 and 1200 rpm throughout the mixing process.

[0690] ii. Solution of component D1 in component D4

[0691] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0692] iii. Dispersed components D2 and D3

[0693] Component D2 and component D3 can be dispersed into the component D1A solution. The solid content in this step can be 1-15%.

[0694] iv. Dispersed component B

[0695] Component B may be added and mixed for 30-90 minutes. The solids content in this step may be 5-30%.

[0696] v. Dispersed component A

[0697] Next, all components A can be dispersed into the slurry for 90-120 minutes. The solid content in this step can be 40-70%.

[0698] v. Dispersed component D1B

[0699] Finally, the component D1B solution can be mixed into the slurry for 30-60 minutes. The solid content in this step can be 45-65%.

[0700] Example of anode spacer interface slurry mixing process step 16: Four-stage addition of component D1A

[0701] i. Mixing speed and equipment

[0702] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers and a low shear anchor agitator or a low shear helical blade. Throughout the mixing process, the mixing speed can be maintained as follows:

[0703] ■ Low shear shaft between 10 and 55 rpm

[0704] ■High shear shaft between 0 and 1500 rpm

[0705] ii. Solution of component D1 in component D4

[0706] First, component D1A and component D1B are dissolved in component D4 to form two solutions, 0.5 to 3 wt. % and 25 to 60 wt. %, respectively.

[0707] iii. Dispersed components D2 and B

[0708] A portion of the component D1 solution (between 55 and 90%), component D2 and component B may be mixed for between 60 and 180 minutes. After this step, the solids content may be between 5 and 20 wt.%.

[0709] iv. Dispersed component A

[0710] Half of component A can be added to the mixing vessel; the solution can be mixed for 60 to 240 minutes. After this step, the slurry characteristics can include a solids content between 25 and 55 wt.%. The other half of component A can be added to the slurry. 10% to 45% of the component D1A solution can be added at this time. The slurry can be mixed for 120 minutes to 16 hours. After this step, the solids content can be between 40 and 75 wt.%.

[0711] v. The remainder of the dispersed component D1A

[0712] At this point 10% to 45% of the component D1A solution may be added. The slurry may be mixed for between 30 and 60 minutes. After this step, the solids content may be between 40 and 70 wt.%.

[0713] vi. Dispersed component D1B

[0714] The component D1B solution and the remaining component D1A solution can be added to the slurry. During this step, some solvent can also be added to adjust the slurry viscosity. The slurry can be mixed between 30 minutes and 16 hours.

[0715] vii. Target solids percentage

[0716] Some co-solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30 minutes to 120 minutes. The final slurry properties may look like this:

[0717] -d10<15μm, d50<30μm, d90<60μm, d99<100μm

[0718] -Hegman gauge <80μm

[0719] - Solids content between 40 and 65% by weight

[0720] -Viscosity between 1100 and 2800 cps at 85 Hz

[0721] An alternative method of mixing the solid electrolyte components is also provided, similar to the discussion above for the other layers.

[0722] Specifically, the order in which the particle groups of different materials are added to the mixture must be carefully selected in order to facilitate the distribution of the component particles, provide optimal density and maintain the functionality of the component materials. Smaller particles tend to be interspersed among larger particles. In order to achieve this effectively, the uniformity of the distribution of larger particles must first be determined. In addition, in order to obtain the highest possible gravimetric analysis capability, the total content of each component material can be divided into several groups to design the distribution of large particle groups relative to smaller particle groups.

[0723] In view of the composite volume of the anode-separator layer, it can be defined as:

[0724] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0725] -wherein component A corresponds to the anode active material

[0726] -wherein component B corresponds to an ion-conducting solid polymer

[0727] -where component C corresponds to the free volume

[0728] -where component D corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[0729] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0730] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0731] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0732] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0733] Taking into account the above design criteria, the order in which the components of the anode-separator layer are combined by a mixing process to form a mixture of components A, B, C and D is specified below:

[0734] - Components A2 and B1 can be combined in a step-wise manner and can be mixed with a portion of component D to provide a discrete group

[0735] - A portion of component B2 can be added to the mixture by further adding a portion of component D

[0736] - Component B2 and the remainder of component D may be added gradually to the mixture until the mixture may include the sum of components A2, B1, B2 and D

[0737] A further limitation of the above strategy involves the use of a discontinuous binder medium as part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without inhibiting the transfer of charged species at the interface between the active material of the electrode and the ion-conductive particles dispersed throughout the battery layer or between the polymer solid particles forming the spacer layer. In order to deploy this strategy, staged mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid electrolyte. This ion-conductive powder-coated active material can then be mixed with a binder carrier that is resistant to dissolving agents in the slurry solvent. After mixing the solid electrolyte-coated active material and the non-soluble binder carrier, an additional soluble binder component can be added to adjust the mechanical durability of the electrode without compromising the functionality of the ion-conductive and electroactive materials.

[0738] One version of this process can be described as follows:

[0739] Step 1, components A2 and B1 can be combined in a stepwise manner and can be mixed with a portion of component D to provide a dispersed group

[0740] Step 2, the mixture of components A2 and B1 can be mixed with component D1A (insoluble binder) to provide A2, B1 and D 1A Dispersion of particles

[0741] Step 3, a portion of component B2 can be mixed with component D1B (soluble binder) is added to the mixture together

[0742] Step 4, Component B2 and Component D 1B The remainder of the (soluble binder) may be gradually added to the mixture until the mixture may include all of components A2, B1, B2 and D.

[0743] To facilitate the desired distribution of the above components, the following criteria can be applied to guide component particle size distribution optimization:

[0744] The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4.

[0745] The most common particle size of the anode active material component A1 can be less than 30 microns, greater than 5 microns or 1 micron.

[0746] - The most common particle size of cathode active material component A2 can be >0.5 micron, >1 micron, <5 micron or 1.5 micron

[0747] - The most common particle size of the solid polymer electrolyte component B1 can be <5 μm or >1.6 μm

[0748] - The most common particle size of the solid polymer electrolyte component B2 can be <1.5 μm, >0.35 μm or 0.7 μm

[0749] - The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron

[0750] - The maximum characteristic particle size of the solid polymer electrolyte can be >10 microns, >20 microns or <50 microns

[0751] - The minimum characteristic particle size of the anode active material may be greater than 0.5, >1, >2 or >5 microns, and the maximum characteristic particle size of the cathode may be less than 70, <50, <30, <20 or <15 microns

[0752] - The particle size distribution of a subgroup can be approximated using a lognormal distribution function (including single or multiple components). Multiple components with lognormal distributions can be used to approximate component A and component B

[0753] -

[0754] -Where x is the particle size, μ is the average particle size, and σ is the standard deviation or dispersion

[0755] - The dispersion degree of component A1 may be <0.5, <0.3, <0.2 or <0.15

[0756] - The dispersion of component A2 may be <0.45, <0.4, <0.3, <0.2 or <0.15

[0757] - The dispersion of component B can be <0.7, <0.65 or <0.6

[0758] - The dispersion degree of component B1 may be <0.7, <0.6, <0.5, <0.4, <0.3 or <0.2

[0759] - The dispersion degree of component B2 may be <0.9, <0.8, <0.7, <0.6, <0.5, <0.45 or <0.4

[0760] Anode-spacer interface layer slurry coating process

[0761] In one example, the anode-separator interface layer can be coated, cast, deposited, or laid on the positive electrode, the negative electrode, or both electrodes to ensure high consistency between the separator and the electrodes. The coating process can be performed according to the following configurations:

[0762] - The anode and cathode are coated with the same separator formulation,

[0763] - coating the anode with two different separators in a formulation to optimize the chemical and electrochemical stability between each electrode and separator,

[0764] - Coating a series of layers of different formulations on the anode and / or cathode to allow for a gradient in the composition of the separator, thereby enhancing the chemical and electrochemical stability of the electrode with the separator.

[0765] In order to ensure continuous coverage of the electrode to be coated with the spacer layer, the width of the two coating layers can be the same. The width of the spacer layer can also be slightly larger than the coating width of the supporting electrode.

[0766] The anode spacer interface layer slurry can be applied using one of the coating methods described above (e.g., example procedures 12, 13, 14, 15, or 16) at a speed of 1 to 10 m / min. After coating, the electrode roll passes through a set of four ovens, whose temperatures and fan exhaust can be set as follows:

[0767] - Oven 1, temperature between 40 and 100°C, speed between 300 and 900 rpm,

[0768] - Oven 2, temperature between 50 and 110°C, speed between 300 and 900 rpm,

[0769] - Oven 3, temperature between 60 and 120°C, speed between 300 and 900 rpm,

[0770] - Oven 4, with a temperature between 80 and 140°C and a speed between 300 and 900 rpm.

[0771] Spacer layer (cathode side)

[0772] In one example, the spacer layer of a cell may include a variety of materials that can be characterized as powders in isolated groups, as long as a large number of particles with similar components and properties are included. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer having functionality derived from its composite onto a substrate, which in the case of the present invention can be a current collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, the methods by which the materials can be combined to form a slurry, the characteristics of the slurry, and the casting method of the slurry is provided. The details given below apply to casting the spacer layer on the cathode layer.

[0773] In one example, the composite including the spacer layer and its derived slurry can be formed from a combination of multiple materials with active and passive functions. During the steps required to complete the fabrication of the layer, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry coating.

[0774] The slurry used to apply the spacer layer on the electrode must include one or more solid ion-conducting polymer materials as the primary ion-conducting medium. The primary particle size of the solid ion-conducting polymer material may be between 0.01 and 20 μm.

[0775] The composite (paste or other form) of the spacer layer can be defined as follows:

[0776] - Composition (total) = Component A + Component B + Component C + Component D

[0777] -wherein component A corresponds to the electrode active material (absent)

[0778] -wherein component B corresponds to an ion-conducting solid polymer

[0779] -where component C corresponds to the free volume

[0780] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0781] Thus, the spacer layer slurry may include the following components:

[0782] Component A

[0783] (does not exist)

[0784] Component B

[0785] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0786] Component C

[0787] Component D

[0788] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0789] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0790] - Component D4: dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0791] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0792] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0793] - Component D7: one or more lithium salts, including Li + Cations such as LiClO4, LiAsF6, LiF6, LiF4, LiRFSO3, LiC3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonyl), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide)

[0794] - Component D8: one or more additives for reducing interfacial impedance, such as urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyether and alkylurethane; l-methyl-3-pyrrolidone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(lH)-pyrimidinone; l,5-dimethyl-2-pyrrolidone; alkyl-substituted pyridyl ionic liquids, alkyl-substituted pyrrolidinyl ionic liquids and alkyl-substituted ammonium ionic liquids with counter anions, such as TFSI, PF6, BF4 anions; substituted polyethylene glycols with functional end groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic) or nitriles; polyethylene glycol bis(carboxymethyl) ether; dioctyl sulfosuccinate sodium, lithium or potassium salt; glycolic acid ethoxylated 4-tert-butylphenyl ether; glycolic acid ethoxylated lauryl ether; glycolic acid ethoxylated 4-nonylphenyl ether; glycolic acid ethoxylated oleyl ether; poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium or potassium salt; and sodium, lithium or potassium dodecylbenzenesulfonate.

[0795] In addition to the solvent, the spacer layer slurry should contain the previous components within the following ranges:

[0796] - solid ion-conducting polymer material, between 1 and 98 wt.%

[0797] - Binder, content between 0.1 and 10 wt.%

[0798] - lithium salt content between 0 and 10 wt%,

[0799] - The additive content ranges from 15% to 95%,

[0800] - The surfactant content is between 0 and 5 wt%.

[0801] The composite volume of the spacer layer can be defined as

[0802] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0803] -wherein component A corresponds to the electrode active material (absent)

[0804] -wherein component B corresponds to an ion-conducting solid polymer

[0805] -where component C corresponds to the free volume

[0806] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0807] -The volume percentage of component A can be 0

[0808] - The volume percentage of component B can be >80%, >85%, >90%, >95, or >97%

[0809] - The volume percentage of component C may be <20%, <15%, <10%, <5%, or <3%

[0810] - The volume percentage of component D may be <20%, <15%, <10%, <5%, or <3%

[0811] - The sum of the volume percentages of components C and D may be <20%, <15%, <10%, <5%, or <3%

[0812] The size of the particles, including the powder forms of Group B, may also be described by:

[0813] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0814] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0815] - In the volume % including component B, the size distribution is determined by the average value B1,mean >B mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component B, identified by B2, belongs to B 2,mean mean A group of particles located in the spaces between larger particles

[0816] Before it is applied, the spacer slurry can be characterized as:

[0817] -Viscosity between 500 and 2200 cps at 85 Hz

[0818] - Solids content between 40% and 55%

[0819] -Hegman gauge below 90μm or below 5μm

[0820] - Particle size distribution is as follows: d10 < 1 μm, d50 < 15 μm, d90 < 60 μm, d99 < 100 μm

[0821] A representative particle size distribution curve is shown in Fig.15 As shown in the curve graph 1500. In addition, Fig.16 A representative viscosity curve is shown in graph 1600 of , where viscosity is inversely proportional to shear rate.

[0822] The thickness of the spacer layer after calendering can be between 5 and 50 μm. In a low humidity environment, calendering can be performed between room temperature (20°C) and 140°C.

[0823] Spacer slurry mixing process

[0824] An example procedure for forming a spacer slurry is provided below.

[0825] Example of spacer slurry mixing process Step 17: Two separate starting suspensions of component B in component D4 and component D3+D6 in component D4 are combined in two stages

[0826] i. Mixing speed and equipment

[0827] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[0828] ■ Low shear shaft between 10 and 55 rpm

[0829] ■High shear shaft between 0 and 1500 rpm

[0830] ​ ii. Suspension 1: Solution of components D1 and D3 in component D4

[0831] First, component D1 can be dissolved in component D4 to form solutions of 1% and 15% by weight. After component D1 is dissolved, component D3 can be added to the solution and mixed for 30 to 90 minutes.

[0832] iii. Suspension 1: Dispersed component D6

[0833] Component D6 may then be added and mixed for between 30 and 90 minutes. An ultra high shear rotor / stator mixer may be used to stabilize / homogenize the suspension. The suspension may be characterized as follows:

[0834] -d10<1μm, d50<5μm, d90<10μm, d99<30μm

[0835] -Hegman gauge <50μm

[0836] - Solids content between 40 and 65% by weight

[0837] *Alternatively, the previous suspension may be prepared by first adding component D6, then component D3, and finally component D1. The suspension properties should be the same as those described above.

[0838] iv. Suspension 2: Disperse component B in component D4

[0839] In a separate mixing container, component B can be mixed with component D4 for 30 to 180 minutes with a solid content between 70 and 95 wt.%. After this step, component D4 can be added to the mixing container and mixed for 30 to 90 minutes. The slurry properties can then be:

[0840] -d10<1μm, d50<2μm, d90<15μm, d99<30μm

[0841] -Hegman gauge <50μm

[0842] - Solid content between 30 and 60 wt.%

[0843] v. Disperse suspension 1 into suspension 2 in two stages

[0844] Half of the suspension 1 containing components D6, D1 and D3 in D4 can be added to the suspension 2 in step iv above and mixed for 30 to 120 minutes. After this step, the solid content can be between 30 and 60 wt.%. The remaining half of the suspension 1 containing components D6, D1 and D3 in D4 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step, the slurry characteristics are:

[0845] -d10<1μm, d50<2μm, d90<15μm, d99<30μm

[0846] -Hegman gauge <70μm

[0847] - Solid content between 30 and 60 wt.%

[0848] - At 85 Hz, the viscosity is between 2000 and 4500 centipoise.

[0849] vi. Target solid percentage

[0850] Component D4 can then be added stepwise to adjust the slurry viscosity to the final target. A mixing step of 30 to 60 minutes can be performed after each addition. The slurry can also be mixed under vacuum for 30 to 120 minutes before coating. A sieving step can be used to obtain the desired particle size distribution.

[0851] Fig.17 A process flow diagram 1700 of an example process step 17 is depicted in FIG.

[0852] Example of spacer slurry mixing process Step 18: Add a single suspension of component D6 in D4 to component B in three steps

[0853] i. Mixing speed and equipment

[0854] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[0855] ■ Low shear shaft between 10 and 55 rpm

[0856] ■High shear shaft between 0 and 1500 rpm

[0857] ii. Suspension 1: Component D6 in Component D4

[0858] Component D6 can be suspended in component D4 at a concentration of 40 to 60 wt.%. The suspension can be characterized by the following particle size distribution: d10 <1 μm, d50 <2 μm, d90 <15 μm, d99 <30 μm.

[0859] iii. Disperse component B in part of suspension 1

[0860] Component B and component D1 can be added to one third of the suspension in step ii to bring the solids content to between 50% and 65%. The slurry can be mixed for 30 to 120 minutes. Another third of the suspension in step ii can be added to the slurry to reduce the solids content to between 45% and 60%. The slurry can be mixed for 30 to 120 minutes. The last third of the suspension in step ii can be added and mixed for 30 to 16 hours. After this step, the Hegmann gauge should be below 100 μm and the solids content should be between 40% and 55%.

[0861] iv. Target solid percentage

[0862] Some solvent may be added gradually to adjust the slurry viscosity to the final target.

[0863] Fig.18 A process flow diagram 1800 of an example process step 18 is depicted in FIG.

[0864] Example of spacer slurry mixing process Step 19: Add a single suspension of component D6 in D4 to component B in two steps

[0865] i. Mixing speed and equipment

[0866] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[0867] ■ Low shear shaft between 10 and 40 rpm

[0868] ■High shear shaft between 0 and 3500 rpm

[0869] ii. Suspension of component D6 in component D4

[0870] Half of component D6 may be suspended in component D4 at a concentration between 45 and 60 wt. % and mixed for between 30 and 120 minutes.

[0871] iii. Dispersed component B

[0872] Component B and component D1 may be added to the suspension along with component D4, with a target solids content between 50 and 70 wt.%. The slurry may be mixed for 30 to 120 minutes.

[0873] iv. the remainder of the dispersed component D6

[0874] Component D6 and the remaining half of component D4 can be added to the mixing vessel to bring the solids content to between 45 and 60 wt.%. The slurry can be mixed for 30 to 120 minutes. After this step, the Hegmann pressure gauge should be below 90 μm. Additional component D4 can be added stepwise to adjust the slurry viscosity to the final target.

[0875] Example of a spacer slurry mixing process, step 20: Two separate starting suspensions of component B in component D4 and component D6 in component D4 are combined in three stages

[0876] i. Mixing speed and equipment

[0877] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[0878] ■ Low shear shaft between 10 and 45 rpm

[0879] ■High shear shaft between 0 and 1300 rpm

[0880] ii. Suspension 1: Suspension of component D4 and component D6

[0881] Component D6 can first be suspended in a solvent at a concentration of 40 to 60 wt.%. The suspension can be characterized by the following particle size distribution: d10 <1 μm, d50 <2 μm, d90 <15 μm, d99 <30 μm.

[0882] iii. Suspension 1: Dispersed component D1

[0883] Then, component D1 is added to the suspension and mixed for 30 minutes to 16 hours. After mixing, the suspension has a Hegmann gauge of <80 μm and a solids content of between 40 and 65 wt.%.

[0884] iv. Suspension 2: Dispersed component B

[0885] In a separate mixing vessel, component B can be mixed with a portion of component D4 for 30 to 180 minutes at a solids content between 70 and 95 wt.%. After this step, an additional portion of component D4 can be added to the mixing vessel and mixed for 30 to 90 minutes to reach a solids content between 40 and 65 wt.%.

[0886] v. Disperse suspension 1 into suspension 2 in three stages

[0887] One third of suspension 1 containing components D6 and D4 can be added to the slurry of step iv and mixed for 30 to 120 minutes. The solid content can be between 40 and 65 wt.%, and the Hegmann gauge is <40 μm. Two thirds of suspension 2 can be added to the slurry and mixed for 30 to 120 minutes. The solid content can be between 35 and 63 wt.%, and the Hegmann gauge is <40 μm. The last third of suspension 2 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step, the slurry properties are:

[0888] -Hegman gauge <40μm

[0889] - Solid content between 30 and 60 wt.%

[0890] - At 85 Hz, the viscosity is between 3500 and 4500 centipoise.

[0891] vi. Target solid percentage

[0892] Component D4 can then be added stepwise to adjust the slurry viscosity to the final target. A mixing step of 30 to 60 minutes can be performed after each addition. The slurry can also be mixed under vacuum for 30 to 120 minutes before coating.

[0893] Table 4 provides an example of a spacer slurry mixing process.

[0894] Table 4: For LiNi 0.8 Mn 0.1 Co 0.1 Example of O2(NMC811) (cathode active material) and graphite (anode active material), spacer slurry mixing process.

[0895]

[0896] The slurry particle size distribution was evaluated using a Malvern Mastersizer 3000 laser particle size analyzer. For the spacer layer, the target dry thickness can be less than 30 microns. Therefore, it would be desirable to achieve a particle size distribution in which most particles are below the target thickness. This has been achieved by the example process 17 shown in the table. In addition, as shown in the first cycle efficiency, the best full unit performance can also be achieved by the spacer slurry mixing example process 17.

[0897] An alternative approach of mixing solid electrolyte components is discussed again.

[0898] For example, the order in which the particle groups of different materials are added to the mixture must be carefully selected in order to facilitate the distribution of the component particles, provide optimal density and maintain the functionality of the component materials. Smaller particles tend to be interspersed among larger particles. To achieve this effectively, the uniformity of the distribution of the larger particles must first be determined. In addition, in order to obtain the highest possible gravimetric analysis capability, the total content of each component material can be divided into several groups to design the distribution of the large particle group relative to the smaller particle group.

[0899] Given the previous definition of the composite volume of the spacer layer, it is defined as:

[0900] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C

[0901] -wherein component A corresponds to an ion-conducting solid polymer

[0902] -where component B corresponds to the free volume

[0903] -where component C corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[0904] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[0905] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A 2,mean Can be less than A mean Size distribution

[0906] In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component A, identified by A2, belongs to A 2,mean mean A group of particles located in the spaces between larger particles

[0907] Taking into account the above design criteria, the following specifies the order in which the components of the separator coated on the cathode layer can be combined by a mixing process to form a mixture of components A, B and C:

[0908] ​- A portion of component A1 can be mixed with a portion of component C to provide a dispersed population of A1 particles

[0909] Another portion of component A1 may be mixed with a portion of component A2 and component C to provide a dispersed population of A1 particles

[0910] - Component A2 and the remainder of component C can be added gradually to the mixture until the mixture can include all of components A1, A2, B and C.

[0911] To facilitate the desired distribution of the above components, the following criteria can be used to guide the optimization of the component particle size distribution:

[0912] -The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron or <0.2 micron

[0913] - The maximum characteristic particle size of the solid polymer electrolyte can be >1.5 microns, <2.0 microns or <2.5 microns

[0914] - The particle size distribution of the subgroup can be approximated using a lognormal distribution function (including single or multiple components). Component A can be approximated using multiple components (A1 and A2) with lognormal distributions

[0915] -

[0916] -Where x is the particle size, μ is the mean particle size, and σ is the standard deviation or dispersion

[0917] - The dispersion degree of component A1 may be <0.75, <0.6, <0.5, <0.4, <0.3, <0.2 or <0.15

[0918] - The dispersion of component A2 may be <0.8, <0.7, <0.6, <0.5, <0.45, <0.4 or <0.3

[0919] Spacer coating process

[0920] In one example, the spacer can be coated, cast, deposited or laid on the positive electrode, the negative electrode or both electrodes to ensure a high degree of consistency between the spacer layer and the electrodes. The coating process can be performed according to the following configurations:

[0921] i. The anode and cathode are coated with the same separator formulation,

[0922] ii. coating the anode with two different separator formulations to optimize the chemical and electrochemical stability between each electrode and separator,

[0923] iii. Coating a series of layers of different formulations on the anode and / or cathode to allow for a gradient in the composition of the separator, thereby enhancing the chemical and electrochemical stability of the electrode with the separator.

[0924] To ensure continuous coverage of the electrode to be coated with the separator layer, the width of the two coating layers can be the same. The width of the separator layer can also be slightly larger than the coating width of the supporting electrode.

[0925] The spacer layer slurry can be applied at a speed of 1 to 10 m / min using one of the coating methods described above (e.g., example procedures 17, 18, 19, or 20). After coating, the electrode roller passes through a set of multiple ovens, where drying conditions can be set to achieve an evaporation rate range of 5-70 g / min. This range of values ​​can be optimized to reduce the migration or spatial gradient of component D1 (binder), the network distribution of component B (solid ion conductive polymer material), the optimized uniformity of the coating weight over the coating width, and good coating adhesion (≥10 gf / in). The latter parameter may be important for the subsequent stamping of the electrode without affecting the integrity of the coating, with delamination occurring on the surface or along the edge of the stamped electrode.

[0926] Characterization of the two-dimensional distribution of polymer electrolytes in the spacer layer

[0927] The two-dimensional distribution of component B was quantified by SEM-EDS images. Fig.19 The surface of the spacer coating is shown in the SEM image 1900, where component B is highlighted in white and the background is shown in black.

[0928] - Using nearest neighbor distance (NND) analysis, the 2D distribution of polymer electrolytes can be clustered with an average NND between 3-10 μm.

[0929] - The maximum Feret distance (the longest distance between two points on the boundary of the polymer electrolyte particle) can be between 1 and 30 μm.

[0930] - The particle size can be between 0.5-180 μm 2 between.

[0931] - The circularity of the particles in the spacer, determined by Defined, can be between 0.2-1.0.

[0932] Spacer layer (anode side)

[0933] In one example, the spacer layer of the cell may include a variety of materials that can be characterized as powders in isolated groups, as long as a large number of particles with similar components and properties are included. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer with functionality derived from its composite onto a substrate, which in the case of the present invention can be a current collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, the methods by which the materials can be combined to form a slurry, the characteristics of the slurry, and the casting method of the slurry is provided. The details given below apply to casting the spacer layer on the anode layer.

[0934] In one example, the composite including the spacer layer and its derived slurry can be formed from a combination of multiple materials with active and passive functions. During the steps required to complete the fabrication of the layer, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry coating.

[0935] The slurry used to apply the spacer layer on the electrode must include one or more solid ion-conducting polymer materials as the primary ion-conducting medium. The primary particle size of the solid ion-conducting polymer material may be between 0.01 and 20 μm.

[0936] The composite (paste or other form) of the spacer layer can be defined as follows:

[0937] - Composition (total) = Component A + Component B + Component C + Component D

[0938] -wherein component A corresponds to the electrode active material (absent)

[0939] -wherein component B corresponds to an ion-conducting solid polymer

[0940] -where component C corresponds to the free volume

[0941] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0942] Thus, the spacer layer slurry may include the following components:

[0943] Component A

[0944] (does not exist)

[0945] Component B

[0946] - one or more solid ion-conducting polymer materials, as ion-conducting agents, with a primary particle size between 0.01 and 20 μm

[0947] Component C

[0948] Component D

[0949] - Component D1: a binder comprising at least one compound selected from the group consisting of polyether, polyester, carboxymethyl cellulose or a polymer based on at least one monomer (e.g., methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride)

[0950] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[0951] - Component D4: dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[0952] - Component D5: one or more inorganic additives for reducing interfacial resistance, such as LiNbO3, LiTaO3, LiNbxTa1-xO3, BaTiO3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 microns

[0953] - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte in the solid electrolyte layer and providing supplementary functions, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2 and compounds derived from combinations thereof, including possible addition of Li2O, with a primary particle size between 0.01 and 10 μm

[0954] - Component D7: one or more lithium salts, including Li + Cations such as LiClO4, LiAsF6, LiF6, LiF4, LiRFSO3, LiC3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonyl), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide)

[0955] - Component D8: one or more additives for reducing interfacial impedance, such as urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyether and alkylurethane; l-methyl-3-pyrrolidone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(lH)-pyrimidinone; l,5-dimethyl-2-pyrrolidone; alkyl-substituted pyridyl ionic liquids, alkyl-substituted pyrrolidinyl ionic liquids and alkyl-substituted ammonium ionic liquids with counter anions, such as TFSI, PF6, BF4 anions; substituted polyethylene glycols with functional end groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic) or nitriles; polyethylene glycol bis(carboxymethyl) ether; dioctyl sulfosuccinate sodium, lithium or potassium salt; glycolic acid ethoxylated 4-tert-butylphenyl ether; glycolic acid ethoxylated lauryl ether; glycolic acid ethoxylated 4-nonylphenyl ether; glycolic acid ethoxylated oleyl ether; poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium or potassium salt; and sodium, lithium or potassium dodecylbenzenesulfonate.

[0956] In addition to the solvent, the spacer layer slurry should contain the previous components within the following ranges:

[0957] i. Solid ion-conducting polymer material, between 1 and 98 wt.%

[0958] ii. Binder, content between 0.1 and 10 wt.%

[0959] iii. The lithium salt content is between 0 and 10 wt%,

[0960] iv. The additive content is between 15% and 95%,

[0961] v. The surfactant content is between 0 and 5 wt%.

[0962] The composite volume of the spacer layer can be defined as

[0963] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C +%Volume 组分D

[0964] -wherein component A corresponds to the electrode active material (absent)

[0965] -wherein component B corresponds to an ion-conducting solid polymer

[0966] -where component C corresponds to the free volume

[0967] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[0968] -The volume percentage of component A can be 0

[0969] - The volume percentage of component B can be >80%, >85%, >90%, >95, or >97%

[0970] - The volume percentage of component C may be <20%, <15%, <10%, <5%, or <3%

[0971] - The volume percentage of component D may be <20%, <15%, <10%, <5%, or <3%

[0972] - The sum of the volume percentages of components C and D may be <20%, <15%, <10%, <5%, or <3%

[0973] The size of the particles, including the powder forms of Group B, may also be described by:

[0974] - In the volume % comprising component B, it may be assigned an average particle size value B mean , the percentage of the total group identified as B1 that will be characterized as having a mean value of B 1,mean Can be greater than B mean Size distribution

[0975] - In the volume percentage including component B, it can be assigned an average particle size value B mean , the percentage of the total group identified as B2 that will be characterized as having a mean value of B 2,mean Can be smaller than B mean Size distribution

[0976] - In the volume % including component B, the size distribution is determined by the average value B 1,mean >B mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component B, identified by B2, belongs to B 2,mean mean A group of particles located in the spaces between larger particles

[0977] Before it is applied, the spacer slurry can be characterized as:

[0978] i. At 85Hz, the viscosity is between 500 and 2200cps

[0979] ii. Solid content between 40% and 55%

[0980] iii. Hegman gauge is less than 90μm or less than 50μm

[0981] ​iv. Particle size distribution is as follows: d10<1μm, d50<15μm, d90<60μm, d99<100μm

[0982] The thickness of the spacer layer after calendering can be between 5 and 50 μm. In a low humidity environment, calendering can be performed between room temperature (20°C) and 140°C.

[0983] Spacer slurry mixing process

[0984] An example procedure for forming a spacer slurry is provided below.

[0985] Example of spacer slurry mixing process Step 21: Two independent starting suspensions of component B in component D4 and component D3+D6 in component D4 are combined in two stages

[0986] i. Mixing speed and equipment

[0987] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[0988] ■ Low shear shaft between 10 and 55 rpm

[0989] ■High shear shaft between 0 and 1500 rpm

[0990] ii. Suspension 1: Solution of components D1 and D3 in component D4

[0991] First, component D1 can be dissolved in component D4 to form solutions of 1% and 15% by weight. After component D1 is dissolved, component D3 can be added to the solution and mixed for 30 to 90 minutes.

[0992] iii. Suspension 1: Dispersed component D6

[0993] Component D6 may then be added and mixed for between 30 and 90 minutes. An ultra high shear rotor / stator mixer may be used to stabilize / homogenize the suspension. The suspension may be characterized as follows:

[0994] -d10<1μm, d50<5μm, d90<10μm, d99<30μm

[0995] -Hegman gauge <50μm

[0996] - Solids content between 40 and 65% by weight

[0997] *Alternatively, the previous suspension may be prepared by first adding component D6, then component D3, and finally component D1. The suspension properties should be the same as those described above.

[0998] iv. Suspension 2: Disperse component B in component D4

[0999] In a separate mixing container, component B can be mixed with component D4 for 30 to 180 minutes with a solid content between 70 and 95 wt.%. After this step, component D4 can be added to the mixing container and mixed for 30 to 90 minutes. The slurry properties can then be:

[1000] -d10<1μm, d50<2μm, d90<15μm, d99<30μm

[1001] -Hegman gauge <50μm

[1002] - Solid content between 30 and 60 wt.%

[1003] v. Disperse suspension 1 into suspension 2 in two stages

[1004] Half of the suspension 1 containing components D6, D1 and D3 in D4 can be added to the suspension 2 in step iv above and mixed for 30 to 120 minutes. After this step, the solid content can be between 30 and 60 wt.%. The remaining half of the suspension 1 containing components D6, D1 and D3 in D4 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step, the slurry characteristics are:

[1005] -d10<1μm, d50<2μm, d90<15μm, d99<30μm

[1006] -Hegman gauge <70μm

[1007] - Solid content between 30 and 60 wt.%

[1008] - At 85 Hz, the viscosity is between 2000 and 4500 centipoise.

[1009] vi. Target solid percentage

[1010] Component D4 can then be added stepwise to adjust the slurry viscosity to the final target. A mixing step of 30 to 60 minutes can be performed after each addition. The slurry can also be mixed under vacuum for 30 to 120 minutes before coating. A sieving step can be used to obtain the desired particle size distribution.

[1011] Fig.17 A process flow diagram 1700 of an example process step 21 is depicted in FIG.

[1012] Example of spacer slurry mixing process Step 22: Add a single suspension of component D6 in D4 to component B in three steps

[1013] i. Mixing speed and equipment

[1014] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[1015] ■ Low shear shaft between 10 and 55 rpm

[1016] ■High shear shaft between 0 and 1500 rpm

[1017] ii. Suspension 1: Component D6 in Component D4

[1018] Component D6 can be suspended in component D4 at a concentration of 40 to 60 wt.%. The suspension can be characterized by the following particle size distribution: d10 <1 μm, d50 <2 μm, d90 <15 μm, d99 <30 μm.

[1019] iii. Disperse component B in part of suspension 1

[1020] Component B and component D1 can be added to one third of the suspension in step ii to bring the solids content to between 50% and 65%. The slurry can be mixed for 30 to 120 minutes. Another third of the suspension in step ii can be added to the slurry to reduce the solids content to between 45% and 60%. The slurry can be mixed for 30 to 120 minutes. The last third of the suspension in step ii can be added and mixed for 30 to 16 hours. After this step, the Hegmann gauge should be below 100 μm and the solids content should be between 40% and 55%.

[1021] iv. Target solid percentage

[1022] Some solvent may be added gradually to adjust the slurry viscosity to the final target.

[1023] Fig.18 A process flow diagram 1800 of an example process step 22 is depicted in FIG.

[1024] Example of spacer slurry mixing process Step 23: Add a single suspension of component D6 in D4 to component B in two steps

[1025] i. Mixing speed and equipment

[1026] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[1027] ■ Low shear shaft between 10 and 40 rpm

[1028] ■High shear shaft between 0 and 3500 rpm

[1029] ii. Suspension of component D6 in component D4

[1030] Half of component D6 may be suspended in component D4 at a concentration between 45 and 60 wt. % and mixed for between 30 and 120 minutes.

[1031] iii. Dispersed component B

[1032] Component B and component D1 may be added to the suspension along with component D4, with a target solids content between 50 and 70 wt.%. The slurry may be mixed for 30 to 120 minutes.

[1033] iv. the remainder of the dispersed component D6

[1034] Component D6 and the remaining half of component D4 can be added to the mixing vessel to bring the solids content to between 45 and 60 wt.%. The slurry can be mixed for 30 to 120 minutes. After this step, the Hegmann pressure gauge should be below 90 μm. Additional component D4 can be added stepwise to adjust the slurry viscosity to the final target.

[1035] Example of a spacer slurry mixing process, step 24: Two separate starting suspensions of component B in component D4 and component D6 in component D4 are combined in three stages

[1036] i. Mixing speed and equipment

[1037] Dispersion of the components can be achieved by a combination of a single shaft mixer equipped with a sawtooth high shear disperser and a multi-shaft mixer equipped with multiple high shear dispersers, as well as a low shear anchor agitator, a low shear helical blade, or an ultra-high shear rotor / stator mixer. Throughout the mixing process, the mixing speed can be maintained as follows:

[1038] ■ Low shear shaft between 10 and 45 rpm

[1039] ■High shear shaft between 0 and 1300 rpm

[1040] ii. Suspension 1: Suspension of component D4 and component D6

[1041] Component D6 can first be suspended in a solvent at a concentration of 40 to 60 wt.%. The suspension can be characterized by the following particle size distribution: d10 <1 μm, d50 <2 μm, d90 <15 μm, d99 <30 μm.

[1042] iii. Suspension 1: Dispersed component D1

[1043] Then, component D1 is added to the suspension and mixed for 30 minutes to 16 hours. After mixing, the suspension has a Hegmann gauge of <80 μm and a solids content of between 40 and 65 wt.%.

[1044] iv. Suspension 2: Dispersed component B

[1045] In a separate mixing vessel, component B can be mixed with a portion of component D4 for 30 to 180 minutes at a solids content between 70 and 95 wt.%. After this step, an additional portion of component D4 can be added to the mixing vessel and mixed for 30 to 90 minutes to reach a solids content between 40 and 65 wt.%.

[1046] v. Disperse suspension 1 into suspension 2 in three stages

[1047] One third of suspension 1 containing components D6 and D4 can be added to the slurry of step iv and mixed for 30 to 120 minutes. The solid content can be between 40 and 65 wt.%, and the Hegmann gauge is <40 μm. Two thirds of suspension 2 can be added to the slurry and mixed for 30 to 120 minutes. The solid content can be between 35 and 63 wt.%, and the Hegmann gauge is <40 μm. The last third of suspension 2 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step, the slurry properties are:

[1048] -Hegman gauge <40μm

[1049] - Solid content between 30 and 60 wt.%

[1050] - At 85 Hz, the viscosity is between 3500 and 4500 centipoise.

[1051] vi. Target solid percentage

[1052] Component D4 can then be added stepwise to adjust the slurry viscosity to the final target. A mixing step of 30 to 60 minutes can be performed after each addition. The slurry can also be mixed under vacuum for 30 to 120 minutes before coating.

[1053] Table 5 provides an example of a spacer slurry mixing process.

[1054] Table 5: For LiNi 0.8 Mn 0.1Co 0.1 Example of O2(NMC811) (cathode active material) and graphite (anode active material), spacer slurry mixing process.

[1055]

[1056] The slurry particle size distribution was evaluated using a Malvern Mastersizer 3000 laser particle size analyzer. For the spacer layer, the target dry thickness can be less than 30 microns. Therefore, it would be desirable to achieve a particle size distribution in which most particles are below the target thickness. This has been achieved by the example process 21 shown in the table. In addition, as shown in the first cycle efficiency, the best full unit performance can also be achieved by the spacer slurry mixing example process 21.

[1057] An alternative method of mixing solid electrolyte components is also discussed. For example, in order to facilitate the distribution of component particles, provide optimal density and maintain the functionality of the component materials, the order in which the particle groups of different materials are added to the mixture must be carefully selected. Smaller particles tend to be scattered among larger particles. In order to achieve this effectively, the uniformity of the distribution of larger particles must first be determined. In addition, in order to obtain the highest possible gravimetric analysis capability, the total content of each component material can be divided into several groups to design the distribution of large particle groups relative to smaller particle groups.

[1058] Given the previous definition of the composite volume of the spacer layer, it is defined as:

[1059] volume 总 =% volume 组分A +%Volume 组分B +%Volume 组分C

[1060] -wherein component A corresponds to an ion-conducting solid polymer

[1061] -where component B corresponds to the free volume

[1062] -where component C corresponds to the volume produced when binders, additives and other functional and non-functional components are present

[1063] - In the volume % comprising component A, it may be assigned an average particle size value A mean , the percentage of the total group identified as A1 will be characterized as having a mean value of A 1,mean Can be greater than A mean Size distribution

[1064] - In the volume percentage including component A, it can be assigned an average particle size value A mean , the percentage of the total group identified as A2 that will be characterized as having a mean value of A2,mean Can be less than A mean Size distribution

[1065] In the volume % including component A, the size distribution is determined by the average value A 1,mean >A mean The particles of the group described in the form account for <100%, <95%, <85%, or <80%, and the remainder of component A, identified by A2, belongs to A 2,mean mean A group of particles located in the spaces between larger particles

[1066] Taking into account the above design criteria, the following specifies the order in which the components of the separator coated on the cathode layer can be combined by a mixing process to form a mixture of components A, B and C:

[1067] - A portion of component A1 can be mixed with a portion of component C to provide a dispersed population of A1 particles

[1068] Another portion of component A1 may be mixed with a portion of component A2 and component C to provide a dispersed population of A1 particles

[1069] - Component A2 and the remainder of component C can be added gradually to the mixture until the mixture can include all of components A1, A2, B and C.

[1070] To facilitate the desired distribution of the above components, the following criteria can be used to guide the optimization of the component particle size distribution:

[1071] -The minimum characteristic particle size of the solid polymer electrolyte can be <1 micron, <0.5 micron or <0.2 micron

[1072] - The maximum characteristic particle size of the solid polymer electrolyte can be >1.5 microns, <2.0 microns or <2.5 microns

[1073] - The particle size distribution of the subgroup can be approximated using a lognormal distribution function (including single or multiple components). Component A can be approximated using multiple components (A1 and A2) with lognormal distributions

[1074] -

[1075] -Where x is the particle size, μ is the mean particle size, and σ is the standard deviation or dispersion

[1076] - The dispersion degree of component A1 may be <0.75, <0.6, <0.5, <0.4, <0.3, <0.2 or <0.15

[1077] ​- The dispersion of component A2 may be <0.8, <0.7, <0.6, <0.5, <0.45, <0.4 or <0.3

[1078] Spacer coating process

[1079] In one example, the spacer can be coated, cast, deposited or laid on the positive electrode, the negative electrode or both electrodes to ensure a high degree of consistency between the spacer layer and the electrodes. The coating process can be performed according to the following configurations:

[1080] i. The anode and cathode are coated with the same separator formulation,

[1081] ii. coating the anode with two different separator formulations to optimize the chemical and electrochemical stability between each electrode and separator,

[1082] iii. Coating a series of layers of different formulations on the anode and / or cathode to allow for a gradient in the composition of the separator, thereby enhancing the chemical and electrochemical stability of the electrode with the separator.

[1083] To ensure continuous coverage of the electrode to be coated with the separator layer, the width of the two coating layers can be the same. The width of the separator layer can also be slightly larger than the coating width of the supporting electrode.

[1084] The spacer layer slurry may be applied using one of the coating methods described above (e.g., example procedures 21, 22, 23, or 24) at a speed of 1 to 10 m / min. After coating, the electrode roll passes through a set of four ovens, the temperature and fan exhaust of which may be set as follows:

[1085] i. Oven 1, temperature between 40 and 100°C, speed between 300 and 900 rpm,

[1086] ii. Oven 2, temperature between 50 and 110°C, speed between 300 and 900 rpm,

[1087] iii. Oven 3, temperature between 60 and 120°C, speed between 300 and 900 rpm,

[1088] iv. Oven 4, with a temperature between 80 and 140°C and a rotation speed between 300 and 900 rpm.

[1089] Characterization of the two-dimensional distribution of polymer electrolytes in the spacer layer

[1090] The two-dimensional distribution of component B was quantified by SEM-EDS images. Fig.19 The surface of the spacer coating is shown in the SEM image 1900, where component B is highlighted in white and the background is shown in black.

[1091] - Using nearest neighbor distance (NND) analysis, the 2D distribution of polymer electrolytes can be clustered with an average NND between 2-5 μm.

[1092] - The maximum Feret distance (the longest distance between two points on the boundary of the polymer electrolyte particle) can be between 1 and 30 μm.

[1093] - The particle size can be between 0.5-180 μm 2 between.

[1094] - The circularity of the particles in the spacer, determined by Defined, can be between 0.2-1.0.

[1095] Label protection strip

[1096] In addition to introducing layers between electrode layers, spacer layers, and collector layers, the combination of the above components can also be facilitated by placing additional layers that can be placed to cover a portion of one or more pre-existing layers. For example, a tab protection layer can be introduced to protect tabs extending from the current collector to prevent short circuits in the battery assembly form. The tab protection layer of the unit can include many materials, which can be characterized as powders in an isolated group as long as they include many particles with similar components and properties. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer with functionality derived from its composite onto a substrate, which in the case of the present invention can be a collector or a previously manufactured electrode, a spacer, or a component comprising a combination thereof. In the following, a description of the component materials, the method by which they can be combined to form a slurry, the characteristics of the slurry, and the casting method of the slurry is provided.

[1097] Composites including interfacial cathode-spacer layers and derived slurries can be formed from a variety of materials with active and passive functions. In the steps required to complete the fabrication of the layers, some of these candidate materials can be deployed on a sacrificial basis during slurry formation and can be removed after slurry casting.

[1098] Additional coatings may be desirable near the electrode coating to prevent shorting when the tabs come into contact with bare current collectors exposed at the electrode edge.

[1099] The complex can be defined as follows:

[1100] -wherein component A corresponds to the electrode active material (absent)

[1101] - wherein component B corresponds to an ion-conducting solid polymer (absent)

[1102] -where component C corresponds to the free volume

[1103] -wherein component D corresponds to adhesives, additives and other functional and non-functional components

[1104] Thus, the tab protection strip slurry may include the following components:

[1105] Component A

[1106] (does not exist)

[1107] Component B

[1108] (does not exist)

[1109] Component C

[1110] Component D

[1111] - Component D1: a binder comprising at least one compound selected from polyethers, polyesters, carboxymethyl cellulose or polymers based on at least one monomer, such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride

[1112] - Component D3: one or more surfactants for slurry uniformity, such as sulfates, sulfonates, phosphates and carboxylates

[1113] - Component D4: dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water

[1114] - Component D6: one or more mechanical integrity additives, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, primary particle size less than 1 μm

[1115] In addition to the solvent, the splice protection paste should contain the previous components within the following ranges:

[1116] - the content of component D1 is between 5 and 100 wt%,

[1117] - the content of component D6 is between 0 and 95 wt%,

[1118] - The content of component D3 is between 0 and 2 wt%.

[1119] Prior to coating, the tab protection paste can be characterized as:

[1120] -Viscosity between 500 and 3000 centipoise at 85 Hz

[1121] -A solid content between 3% and 40%

[1122] -Hegman gauge below 30μm or below 10μm

[1123] - Particle size distribution is as follows: d10 < 1 μm, d50 < 5 μm, d90 < 10 μm, d99 < 30 μm

[1124] The thickness of the tab protection tape after calendering can be between 5 and 40 μm, and the width can be between 3 and 10 mm. The calendering can be performed in a low humidity environment between room temperature (20° C.) and 140° C.

[1125] Splicing slurry mixing process

[1126] The binder may be dissolved in the solvent at a concentration of 1 to 15 wt.%. After the binder is dissolved, a surfactant may be added to the solution and mixed for 30 to 90 minutes. The additives may then be added and mixed for between 30 and 90 minutes. Ultrasonication or homogenization may be required to stabilize the suspension.

[1127] Alternatively, the previous suspension may be prepared by adding the additive first, then the surfactant, and finally the binder. The suspension properties should be the same as those described above.

[1128] Splice protection tape coating process

[1129] Tab protection strips can be applied to the positive tab, the negative tab, or both electrode tabs. They should be applied close to the electrode coating to minimize overlap with the electrode coating and with exposed current collectors between the electrode coating and the tab protection strip coating.

[1130] The tab protection slurry can be applied at a speed of 1 to 10 m / min using one of the coating methods described above. After coating, the electrode roller passes through a set of multiple ovens, where the drying conditions can be set to achieve an evaporation rate range of 0.1-15 g / min. Values ​​within this range can be optimized to reduce migration or spatial gradients of component D1 (binder), network distribution of component B (solid ion-conducting polymer material), optimized uniformity of coating weight over the coating width, and good coating adhesion (≥10 gf / in). The latter parameter may be important for subsequent stamping of the electrode without affecting the integrity of the coating, with delamination occurring on the surface or along the edges of the stamped electrode.

[1131] The methods described herein improve the manufacturing of rechargeable lithium-ion batteries and provide a way to replace the liquid electrolyte component in conventional cells with a solid electrolyte. These methods improve safety by reducing or eliminating the amount of liquid electrolyte in the finished cell, but also provide performance advantages for the resulting devices. In this regard, these methods provide performance benefits by optimizing the energy and power density of the cell through optimizing powder filling strategies, resulting in increased specific capacity, reduced porosity, and lower internal resistance.

[1132] The methods described herein include the phased introduction of the component materials, which are adjusted to provide matching between the material subsystems, as well as filling the free volume of the matrix, thereby providing the functionality of the manufactured components. In addition, the methods of selecting and deploying the materials that support the slurry formulation and casting process increase the integrity and functionality of the individual and combined layers in the composite form. Not only does the order of addition of the materials affect the relative distribution of the component materials, but the methods used to mix these materials once exposed to the intended intermixing also affect the overall distribution of the component materials.

[1133] After mixing the slurry, further complications may be encountered during the casting process as the fluid dynamics of the cast slurry evolve toward the fluid dynamics of a solid film, the properties of which may be sensitive to the parameters defining the path between the liquid and solid states. The described method for combining device layers and solid-phase layered structures during casting of a liquid-phase slurry improves stability without compromising the functionality of the individual materials or the resulting composite structure.

[1134] The mixing and casting methods described herein are used to make solid-state battery slurries and their layers, which, when combined with other operations, can generate entire solid-state battery slurries. The following methods are provided to produce functional cells or batteries:

[1135] Step 1, processing the component powders (components A, B, D1, D2, D5, D6, D7, D8) using various methods (e.g., grinding and sieving) to produce the powder groups described for producing the slurry.

[1136] a. Examples of materials involving particle size design include, in a non-limiting manner, cathode or anode active materials, polymer solid electrolytes, inorganic solid electrolyte materials, inorganic mechanically stable powders, conductive additives, binder materials, salts, etc.

[1137] Step 2, for example, using a combination of laser or white light particle size analysis, scanning electron microscopy, and test sieves, evaluates the particle size distribution of the above materials.

[1138] Step 3, using a combination of high shear and low shear mixing techniques to disperse the components, through their staged combination with each other and the components including the slurry carrier, non-limiting examples of which may include (components D1, D3, D4):

[1139] a. Solvents, adhesives, surfactants, defoamers, thickeners, diluents, etc.

[1140] In step 4, the slurry can be characterized in a staged parallel workflow using techniques such as rheology, particle size analysis, and Hegmann gauges.

[1141] In step 5, the cathode slurry (components A, B, C, D1-D8) can be cast onto one or both sides of the current collector using a roll-to-roll coating technique (eg, slot die coating) to form a cathode layer.

[1142] a. The cathode layer can be dried online after the casting process.

[1143] In step 6, the anode slurry (components A, B, C, D1-D8) can be cast onto one or both sides of the current collector using a roll-to-roll coating technique (eg, slot die coating) to form an anode layer.

[1144] a. The anode layer can be dried online after the casting process.

[1145] In step 7, the anode or cathode structure may be subjected to a calendering process.

[1146] In step 8, the separator slurry (components B, C, D1, D3, D4, D5, D6, D7, D8) can be cast onto one or both sides of the cathode or anode using a roll-to-roll coating technique (e.g., slot die coating).

[1147] a. The layered electrode separator structure can be dried in-line after the casting process.

[1148] In step 9, the layered electrode separator structure may be subjected to a calendaring process.

[1149] At step 10, the layered electrode-separator structure may be subjected to a baking process, including one or both of high temperature and reduced pressure.

[1150] The electrodes may then be inserted into one another, step 11, to align the cathode and anode current collector tabs with the tabs of the other electrodes to form a stack.

[1151] The stacked electrodes may then be packaged in a sealed container (eg, a bag), step 12 .

[1152] Step 13, the unit may then be subjected to a formation routine to condition the unit for use.

[1153] In this way, a slurry for applying a coating to an electrode structure of a solid-state battery cell can be formed using an optimized particle distribution and selective staged component introduction. The technical effect of forming a slurry in this way is that the coating formed thereby can have a reduced porosity and an improved percolation network. In addition, the slurry can form a separator coating including a solid ion conductive polymer material. The technical effect of adding a solid ion conductive polymer material is to reduce the resistance to lithium ion transport and provide mechanical stability in a formed battery.

[1154] In one example, a method includes: dividing a solvent into a plurality of parts according to a sequence of steps, mixing a solid ion-conducting polymer material in a first part of the solvent to form a suspension, for example, formed of polyphenylene sulfide or a liquid crystal polymer, wherein the solid ion-conducting polymer material has a relative humidity greater than 1 x 10 -5S / cm ionic conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is about half of the total solvent content, a first additive is mixed in the suspension, and after the first additive is mixed in the suspension, the second portion of the solvent is mixed with the suspension to form a slurry with a solid content between 25 and 80 wt%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2800 cps at 85 Hz, wherein the mixing includes high shear mixing and low shear mixing, and the low shear is between 10 and 55 rpm. The first example of the method also includes: wherein the high shear is between 0 and 1500 rpm. The second example of the method (optionally including the first example of the method) further includes: wherein the high shear is between 0 and 3500 rpm, and the low shear is between 10 and 40 rpm. The third example of the method (optionally including one or more of the first and second examples of the method) also includes: wherein the high shear is between 0 and 1300 rpm, and the low shear is between 10 and 45 rpm. The fourth example of the method (optionally including one or more of the first to third examples of the method) also includes: wherein the mixing includes mixing under high shear and mixing under low shear at the same time. The fifth example of the method (optionally including one or more of the first to fourth examples of the method) also includes: wherein the amount of the first part of the solvent and the amount of the second part of the solvent are approximately equal. The sixth example of the method (optionally including one or more of the first to fifth examples of the method) also includes: wherein the first additive includes an electrode active material, a binder, a surfactant, or an inorganic ceramic. The seventh embodiment of the method (optionally including one or more of the first to sixth embodiments of the method) also includes that mixing the first additive in the suspension includes: mixing the first additive and one or more other additives in the suspension. An eighth embodiment of the method (optionally including one or more of the first to seventh embodiments of the method) also includes: wherein the first additive is an inorganic ceramic, the one or more other additives are a binder and a surfactant, wherein mixing the first additive and the one or more other additives in a suspension includes: mixing the binder and the surfactant in a third part of the solvent to form a solution, mixing the inorganic ceramic in the solution, and after mixing the inorganic ceramic in the solution, dividing the solution into multiple parts, mixing a part of the solution in the suspension, and then mixing the remaining part of the solution in the suspension.The ninth example of the method (optionally including one or more of the first to eighth examples of the method) also includes: wherein the first additive is an electrode active material, wherein mixing the solid ion conductive polymer material in the first portion of the solvent to form the suspension includes dividing a binder into a plurality of portions, mixing a first portion of the binder in the first portion of the solvent to form a first solution, dividing the first solution into a plurality of portions, mixing an electronic conductor in the first portion of the first solution to form a suspension, and mixing the solid ion conductive polymer material and a second portion of the first solution in the suspension, wherein mixing the first additive in the suspension includes mixing the electrode active material and the remaining portion of the first solution in the suspension. The tenth embodiment of the method (optionally including one or more of the first to ninth embodiments of the method) also includes: wherein the electrode active material is a cathode active material. The eleventh embodiment of the method (optionally including one or more of the first to tenth embodiments of the method) also includes, wherein, mixing the electrode active material with the remaining portion of the first solution in the suspension includes dividing the first additive into a plurality of portions, mixing the first portion of the electrode active material and the third portion of the first solution with the suspension for 45 to 120 minutes, and then mixing the second portion of the electrode active material and the fourth portion of the first solution with the suspension for 2 to 16 hours. The twelfth example of the method (optionally including one or more of the first to eleventh examples of the method) also includes: wherein the viscosity is between 2000 and 2600 cps at 85 Hz. The thirteenth example of the method (optionally including one or more of the first to twelfth examples of the method) also includes: wherein, the electrode active material is an anode active material. The fourteenth embodiment of the method (optionally including one or more of the first to thirteenth embodiments of the method) also includes: after mixing the electrode active material and the remaining portion of the first solution in the suspension, mixing the second portion of the binder with the third portion of the solvent to form a second solution, and mixing the second solution in the suspension. The fifteenth example of the method (optionally including one or more of the first to fourteenth examples of the method) further includes: wherein the solid content is between 25 and 75 wt%. The sixteenth example of the method (optionally including one or more of the first to fifteenth examples of the method) further includes: wherein the viscosity is between 1100 and 2800 cps at 85 Hz.The seventeenth example of the method (optionally including one or more of the first to sixteenth examples of the method) also includes, wherein, mixing the electrode active material and the remaining portion of the first solution in the suspension includes: dividing the electrode active material into a plurality of portions, mixing the first portion of the electrode active material and the third portion of the first solution with the suspension for 45 to 120 minutes, then mixing the second portion of the electrode active material and the fourth portion of the first solution with the suspension for 2 to 16 hours, and then mixing the fifth portion of the first solution with the suspension for 30 to 90 minutes. The eighteenth example of the method (optionally including one or more of the first to seventeenth examples of the method) also includes: wherein, the solid content is between 25 and 65 wt.%. The nineteenth example of the method (optionally including one or more of the first to eighteenth examples of the method) also includes: wherein, the viscosity is between 500 and 2600 cps at 85 Hz. The twentieth example of the method (optionally including one or more of the first to nineteenth examples of the method) further includes: wherein the slurry has a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 140 μm. The twenty-first example of the method (optionally including one or more of the first to twentieth examples of the method) further includes: wherein the d99 particle size of the slurry is less than 100 μm. The twenty-second example of the method (optionally including one or more of the first to twenty-first examples of the method) further includes: wherein the Hegman gauge is less than 80 μm. The twenty-third example of the method (optionally including one or more of the first to twenty-second examples of the method) further includes: wherein the Hegman gauge is less than 50 μm. The twenty-fourth example of the method (optionally including one or more of the first to twenty-third examples of the method) further includes: mixing a second portion of the solvent with the suspension under vacuum to form the slurry.

[1155] In another example, a method for forming a coating on an electrode structure includes: dividing a solvent into a plurality of parts; mixing a solid ion conductive polymer material in a first part of the solvent to form a suspension according to the steps, wherein the solid ion conductive polymer material has a carbon content greater than 1 x 10 -5S / cm ionic conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is about half of the total solvent content; mixing a first additive in the suspension; and after mixing the first additive in the suspension, mixing the second portion of the solvent with the suspension to form a slurry having a solid content between 25 and 80 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2800 cps at 85 Hz, wherein the mixing includes mixing under high shear and mixing under low shear, the low shear being between 10 and 55 rpm; coating the slurry on the electrode structure; drying the coated electrode structure; and calendering the coated electrode structure; wherein the electrode structure includes one of an anode material coating deposited on an anode current collector and a cathode material coating deposited on a cathode current collector; and wherein the adhesion interface between the coating and the electrode structure has a 180° peel strength greater than 200 gf / in.

[1156] In another example, a method includes: dividing a solvent into a plurality of portions; mixing a solid ion-conducting polymer material in a first portion of the solvent with low shear to form a suspension, the solid ion-conducting polymer material having a relative humidity greater than 1 x 10 -5S / cm ionic conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature; mixing a binder in the suspension; and after mixing the binder in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solid content between 25 and 55 wt.%, a d50 particle size of less than 15 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2200 cps at 85 Hz, wherein the mixing includes mixing under high shear and mixing under low shear, and the low shear is between 10 and 55 rpm. The first example of the method also includes: wherein the high shear is between 0 and 1500 rpm. The second example of the method (optionally including the first example of the method) also includes: wherein the high shear is between 0 and 3500 rpm and the low shear is between 10 and 40 rpm. The third example of the method (optionally including one or more of the first and second examples of the method) also includes: wherein the high shear is between 0 and 1300 rpm and the low shear is between 10 and 45 rpm. A fourth example of the method (optionally including one or more of the first to third examples of the method) further includes: wherein the low shear is about 15 rpm. A fifth example of the method (optionally including one or more of the first to fourth examples of the method) further includes: wherein the mixing includes mixing under high shear and mixing under low shear simultaneously. A sixth example of the method (optionally including one or more of the first to fifth examples of the method) further includes: wherein the amount of the first portion of the solvent is about 15% of the total amount of the solvent. A seventh embodiment of the method (optionally including one or more of the first to sixth embodiments of the method) further includes: mixing the binder in the suspension includes mixing the binder and one or more additives in the suspension. An eighth embodiment of the method (optionally including one or more of the first to seventh embodiments of the method) further includes: wherein the one or more additives include an inorganic ceramic, wherein mixing the binder and the one or more additives in the suspension includes mixing the inorganic ceramic in a third portion of the solvent to form a solution, dividing the solution into a plurality of portions, mixing a portion of the solution in the suspension, and then mixing the remaining portion of the solution in the suspension. A ninth embodiment of the method (optionally including one or more of the first to eighth embodiments of the method) also includes: wherein the one or more additives also include a surfactant, wherein mixing the adhesive and the one or more additives in the suspension further includes: first mixing the adhesive and the surfactant in a third portion of a solvent.A tenth embodiment of the method (optionally including one or more of the first to ninth embodiments of the method) further includes, before dispersing the solid ion conductive polymer material in the first portion of the solvent to form the suspension, dividing the inorganic ceramic into a plurality of portions, and mixing the first portion of the inorganic ceramic in the first portion of the solvent. An eleventh embodiment of the method (optionally including one or more of the first to tenth embodiments of the method) further includes, wherein the one or more additives comprise a second portion of the inorganic ceramic, and mixing the binder and the one or more additives in the suspension includes mixing the binder in the suspension, mixing the second portion of the inorganic ceramic with a third portion of the solvent to form a solution, then mixing the binder in the suspension, and mixing the solution in the suspension. A twelfth embodiment of the method (optionally including one or more of the first to eleventh embodiments of the method) further includes, mixing the solution in the suspension includes dividing the solution into a plurality of portions, mixing a portion of the solution in the suspension, and then mixing the remaining portion of the solution in the suspension. The thirteenth example of the method (optionally including one or more of the first to twelfth examples of the method) further includes: wherein the slurry has a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 100 μm. The fourteenth example of the method (optionally including one or more of the first to thirteenth examples of the method) further includes: wherein the Hegman gauge is less than 50 μm. The fifteenth example of the method (optionally including one or more of the first to fourteenth examples of the method) further includes: mixing a second portion of the solvent with the suspension under vacuum to form a slurry.

[1157] In another example, a slurry for forming a coating on an electrode structure, the slurry comprising a solid ion conductive polymer material, for example, formed of polyphenylene sulfide or a liquid crystal polymer, having a relative humidity greater than 1 x 10 -5S / cm, the solid ion conductive polymer material is in a glassy state at room temperature; a solvent; and one or more additives, the one or more additives including electrode active materials, binders, surfactants and inorganic ceramics; wherein the slurry has a solid content between 25 and 80 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm and a viscosity between 500 and 2800 cps at 85 Hz; and if the slurry is formed by a process of sequentially mixing the solid ion conductive polymer material, the solvent and the one or more additives, the process comprises: dividing the solvent into a plurality of parts; mixing the solid ion conductive polymer material in a first part of the solvent to form a suspension, wherein the first part of the solvent is about half of the total solvent content; mixing the one or more additives in the suspension; and after mixing the one or more additives in the suspension, mixing a second part of the solution with the suspension to form the slurry; wherein the mixing comprises mixing under high shear and mixing under low shear, wherein the low shear is between 10 and 55 rpm.

[1158] In another example, a coated hybrid electrode includes: an anode current collector; a cathode current collector; an anode material coating; a cathode material coating; and a solid polymer electrolyte coating formed as a separator; wherein the anode material coating, the cathode material coating and the solid polymer electrolyte coating are formed of a first slurry, a second slurry and a third slurry, respectively, wherein each of the first slurry, the second slurry and the third slurry is formed by the following formula: dividing a solvent into a plurality of parts; mixing a solid ion conductive polymer material in a first part of the solvent to form a suspension according to the order of steps, wherein the solid ion conductive polymer material has a carbon content greater than 1 x 10 -5S / cm ionic conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is about half of the total solvent content; an additive is mixed in the suspension; and after the additive is mixed in the suspension, the second portion of the solvent is mixed with the suspension to form a slurry having a solid content between 25 and 80 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity of 500 to 2800 cps at 85 Hz; wherein the mixing includes mixing under high shear and mixing under low shear, and the low shear is between 10 and 55 rpm. The first example of the coated hybrid electrode also includes, wherein the mixing includes mixing under high shear and mixing under low shear at the same time. The second example of the coated hybrid electrode (optionally including the first example of the coated hybrid electrode) also includes, wherein the Hegman gauge of the first slurry is less than 50 μm, and the viscosity of the first slurry is between 2000 and 2600 cps at 85 Hz. A third example of a coated hybrid electrode (optionally including one or more of the first and second examples of a coated hybrid electrode) further includes: wherein the solid content of the second slurry is between 25 and 65 wt.%, the Hegmann gauge of the second slurry is less than 80 μm, and the viscosity of the second slurry is between 1100 and 2800 centipoise at 85 Hz. A fourth example of a coated hybrid electrode (optionally including one or more of the first to third examples of a coated hybrid electrode) further includes: wherein the solid content of the third slurry is between 25 and 55 wt.%, the d50 particle size of the third slurry is less than 15 μm, and the viscosity of the third slurry is between 500 and 2200 centipoise at 85 Hz. A fifth example of a coated hybrid electrode (optionally including one or more of the first to fourth examples of a coated hybrid electrode) further includes: wherein the solid polymer electrolyte coating is arranged between the anode material coating and the cathode material coating, wherein the composition of the solid polymer electrolyte coating in a first region adjacent to the cathode material coating is different from the composition in a second region adjacent to the anode material coating. The sixth example of the coated hybrid electrode (optionally including one or more of the first to fifth examples of the coated hybrid electrode) also includes: a cathode separator interface coating, which is disposed between the cathode material coating and the solid polymer electrolyte coating, wherein the cathode separator interface coating comprises a solid ion conductive polymer material, wherein the cathode separator interface coating is formed by a fourth slurry, the fourth slurry has a solid content between 25 and 80 wt.%, a d50 particle size less than 30 μm, a Hegman gauge less than 50 μm, and a viscosity between 2000 and 2600 centipoise at 85 Hz.The seventh example of the coated hybrid electrode (optionally including one or more of the first to sixth examples of the coated hybrid electrode) also includes: an anode separator interface coating disposed between the anode material coating and the solid polymer electrolyte coating, wherein the anode separator interface coating comprises a solid ion conductive polymer material, and wherein the anode separator interface coating is formed by a fifth slurry, the fifth slurry having a solid content between 25 and 75 wt.%, a d50 particle size less than 30 μm, a Hegman gauge less than 90 μm, and a viscosity between 500 and 2600 centipoise at 85 Hz. The eighth example of a coated hybrid electrode (optionally including one or more of the first to seventh examples of a coated hybrid electrode) also includes a first tab protection band arranged between the anode current collector and the anode material coating, and a second tab protection band arranged between the cathode current collector and the cathode material coating, wherein the first tab protection band and the second tab protection band are respectively formed by a sixth slurry and a seventh slurry, the solid content of the sixth slurry and the seventh slurry are both between 3 and 40 wt.%, the d50 particle size is less than 5 μm, the Hegmann gauge is less than 30 μm, and the viscosity at 85 Hz is between 500 and 3000 cps.

[1159] In another example, a battery cell comprises: a plurality of hybrid electrodes, each of the plurality of hybrid electrodes comprising: an anode current collector; a cathode current collector; an anode material coating; a cathode material coating; and a solid polymer electrolyte coating formed as a separator; and a sealed bag, the sealed bag containing the plurality of hybrid electrodes; wherein the anode material coating, the cathode material coating and the solid polymer electrolyte coating are respectively formed of a plurality of slurries, wherein each of the plurality of slurries is formed by: dividing a solvent into a plurality of parts; and, in accordance with the order of steps, mixing a solid ion conductive polymer material in at least a first part of the solvent to form a suspension, the solid ion conductive polymer material having a carbon content greater than 1x at room temperature. 10-5S / cm ionic conductivity, and the solid ion conductive polymer material is in a glassy state at room temperature; an additive is mixed in the suspension; and after the additive is mixed in the suspension, a second portion of the solvent is mixed with the suspension to form a composite having a solid content between 25 and 80wt.%, a d50 particle size of less than 30μm, a Hegman gauge of less than 90μm, and a viscosity between 500 and 2800cps at 85Hz; wherein the mixing includes mixing under high shear and mixing under low shear, and the low shear is between 10 and 55rpm. The first example of the battery cell also includes, wherein the mixing includes mixing under high shear and mixing under low shear at the same time. The second example of the battery cell (optionally including the first example of the battery cell) also includes, wherein each of the plurality of hybrid electrodes also includes a first tab protection strip arranged on the anode current collector and a second tab protection strip arranged on the cathode current collector.

[1160] The following claims particularly point out certain combinations and subcombinations regarded as novel and non-obvious. The claims may refer to "an" element or "a first" element or the equivalent thereof. Such claims should be understood to include one or more such elements, neither requiring nor excluding two or more such elements. Other combinations and subcombinations of the disclosed features, functions, elements, and / or properties may be claimed by amendment of the present claims or by presentation of new claims in this or a related application. Such claims, whether broader, narrower, equal, or different in scope to the original claims, are also deemed to be included within the subject matter of the present invention.

Claims

1. A method for forming a slurry, comprising, in order of steps: a first mixing step of mixing a solid ion-conducting polymer material in a first portion of a solvent to form a suspension, The ionic conductivity of the solid ion conductive polymer material at room temperature is greater than 1 x 10 -5 S / cm, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is half of the total content of the solvent; a second mixing, mixing the first additive into the suspension; a third mixing, after mixing the first additive in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solid content between 25 and 80 wt.%, wherein the slurry has a Hegman gauge of less than 90 μm and a viscosity of between 500 and 2800 cps at 85 Hz; Wherein, the first mixing, the second mixing and the third mixing include mixing under a high shear shaft and mixing under a low shear shaft, and the low shear shaft is between 10 and 55 rpm, The slurry has a d10 particle size of less than 1 µm, a d50 particle size of less than 30 µm, a d90 particle size of less than 60 µm, and a d99 particle size of less than 140 µm.

2. The method according to claim 1, wherein: Mixing includes mixing using a multi-shaft mixer, and The high shear shaft is between 1500 and 3500 rpm and the low shear shaft is between 10 and 40 rpm.

3. The method according to claim 1, wherein: The Hegmann gauge is less than 80µm.

4. The method according to claim 1, wherein: The mixing includes mixing on a high shear shaft and mixing on a low shear shaft simultaneously; or The amount of the first part of the solvent is equal to the amount of the second part of the solvent; or The first additive includes an electrode active material, a binder, a surfactant or an inorganic ceramic; or After mixing the first additive in the suspension, mixing a second portion of the solvent with the suspension comprises: mixing a second portion of the solvent with the suspension under vacuum to form the slurry; or Mixing the first additive in the suspension includes mixing the first additive and one or more other additives in the suspension.

5. The method according to claim 4, wherein: The first additive is an inorganic ceramic; The one or more other additives are binders and surfactants; as well as Mixing the first additive and the one or more other additives in the suspension comprises: mixing the binder and the surfactant in a third portion of the solvent to form a solution; mixing the inorganic ceramic in the solution; After mixing the inorganic ceramic in the solution, dividing the solution into a plurality of portions; mixing a portion of the solution in the suspension; and then The remainder of the solution is mixed into the suspension.

6. The method according to claim 1, wherein: The first additive is an electrode active material; Mixing the solid ion-conducting polymer material in the first portion of the solvent to form the suspension comprises: Divide the adhesive into sections; mixing a first portion of the binder with a first portion of the solvent to form a first solution; dividing the first solution into a plurality of portions; mixing an electronic conductor in a first portion of the first solution to form a preliminary suspension; and mixing the solid ion-conducting polymer material and the second portion of the first solution in the preliminary suspension to form the suspension; and Mixing the first additive in the suspension includes: The electrode active material and the remaining portion of the first solution are mixed in the suspension.

7. The method according to claim 6, wherein: Mixing the electrode active material with the remainder of the first solution in the suspension comprises: dividing the first additive into a plurality of portions; mixing the first portion of the electrode active material and the third portion of the first solution with the suspension for 45 to 120 minutes; and then The second portion of the electrode active material and the fourth portion of the first solution are mixed with the suspension for 2 to 16 hours.

8. A slurry for forming a coating on an electrode structure, the slurry comprising: Solid ion-conducting polymer material with a conductivity greater than 1 x 10 -5 S / cm ionic conductivity, the solid ion conductive polymer material being in a glassy state at room temperature; Solvents; as well as one or more additives, the one or more additives comprising an electrode active material, a binder, a surfactant, and an inorganic ceramic; wherein the slurry has a solid content between 25 and 80 wt.%, a Hegman gauge of less than 90 µm, and a viscosity between 500 and 2800 cps at 85 Hz, and the slurry has a d10 particle size of less than 1 µm, a d50 particle size of less than 30 µm, a d90 particle size of less than 60 µm, and a d99 particle size of less than 140 µm; and if the slurry is formed by a process of sequentially mixing the solid ion conductive polymer material, the solvent, and the one or more additives, the process comprises: dividing the solvent into a plurality of portions; mixing the solid ion-conducting polymer material in a first portion of the solvent to form a suspension, wherein the first portion of the solvent is half of the total solvent content; mixing the one or more additives in the suspension; and After mixing the one or more additives in the suspension, mixing a second portion of the solvent with the suspension to form the slurry; The mixing includes mixing under high shear and mixing under low shear, wherein the low shear is between 10 and 55 rpm.

9. A coated hybrid electrode comprising: Anode current collector; cathode current collector; Anode material coating; Cathode material coating; as well as a solid polymer electrolyte coating formed as a spacer; Wherein, the anode material coating, the cathode material coating and the solid polymer electrolyte coating are formed by a first slurry, a second slurry and a third slurry, respectively, wherein each of the first slurry, the second slurry and the third slurry is formed by the following formula: According to the sequence of steps, a solid ion-conducting polymer material is mixed in a first portion of a solvent to form a suspension, wherein the solid ion-conducting polymer material has a relative humidity greater than 1 x 10 -5 S / cm, and the solid ion conductive polymer material is in a glassy state at room temperature, wherein the first portion of the solvent is half of the total solvent content; mixing an additive into the suspension; and After mixing the additive in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solids content between 25 and 80 wt.%, a d50 particle size of less than 30 µm, a Hegman gauge of less than 90 µm, and a viscosity of between 500 and 2800 cps at 85 Hz; Wherein, mixing includes mixing under high shear and mixing under low shear, wherein the low shear is between 10 and 55 rpm, The first slurry has a Hegman gauge of less than 50 μm and a viscosity of the first slurry at 85 Hz between 2000 and 2600 cps; or The solid content of the second slurry is between 25 and 65 wt.%, the Hegman gauge of the second slurry is less than 80 µm, and the viscosity of the second slurry at 85 Hz is between 1100 and 2800 cps; or The solid content of the third slurry is between 25 and 55 wt.%, the d50 particle size of the third slurry is less than 15 μm, and the viscosity of the third slurry at 85 Hz is between 500 and 2200 cps.

10. The coated hybrid electrode according to claim 9, wherein The solid polymer electrolyte coating is disposed between the anode material coating and the cathode material coating; as well as The composition of the solid polymer electrolyte coating in a first region adjacent to the cathode material coating is different from the composition in a second region adjacent to the anode material coating.

11. The coated hybrid electrode of claim 9, further comprising a cathode separator interface coating disposed between the cathode material coating and the solid polymer electrolyte coating; in, The cathode spacer interfacial coating comprises the solid ion-conducting polymer material; and Wherein, the cathode spacer interface coating is formed by a fourth slurry having a solid content between 25 and 80 wt.%, a d50 particle size of less than 30 µm, a Hegman gauge of less than 50 µm, and a viscosity between 2000 and 2600 cps at 85 Hz.

12. The coated hybrid electrode of claim 9, further comprising an anode separator interface coating disposed between the anode material coating and the solid polymer electrolyte coating; in, The anode spacer interface coating comprises the solid ion-conducting polymer material; and Wherein, the anode spacer interface coating is formed by a fifth slurry having a solid content between 25 and 75 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity between 500 and 2600 cps at 85 Hz.

13. The coated hybrid electrode of claim 9, further comprising: A first tab protection tape is disposed between the anode current collector and the anode material coating; as well as A second tab protection tape is disposed between the cathode current collector and the cathode material coating; Wherein, the first splice protection tape and the second splice protection tape are formed by a sixth slurry and a seventh slurry, respectively, and the sixth slurry and the seventh slurry have a solid content between 3 and 40 wt.%, a d50 particle size less than 5µm, a Hegman gauge less than 30µm, and a viscosity between 500 and 3000 centipoise at 85 Hz.

Citation Information

Patent Citations

  • Solid ionically conducting polymer material

    US20170005356A1

  • Solid ionically conducting polymer material

    US20170018781A1

  • Lithium ion battery diaphragm with polymer inorganic coating and preparation method for lithium ion battery diaphragm

    CN103618059A